Solid form of pyrazine substituted nicotinamide, and preparation and use thereof
Patent Information
- Application Number
- JP2024221995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-20
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-26
Smart Images

Figure 2025041735000139 
Figure 2025041735000140 
Figure 2025041735000141
Abstract
Description
[Technical field]
[0001] The present disclosure belongs to the pharmaceutical technical field, and in particular relates to the crystalline form (crystal form) of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (compound A or compound represented by formula (A)) free base or its pharma- ceutically acceptable salt, as well as the preparation method thereof and the use of the compound in the manufacture of a medicament for treating diseases mediated by Bcr-Abl kinase and its mutants, such as chronic myeloid leukemia. The present disclosure also relates to the preparation method of compound A, and to a formulation containing compound A. [Background technology]
[0002] The chemical formula of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Compound A) is C 21 H 17 Its molecular weight is 463.85 g / mol and its chemical structure is: [ka] It is.
[0003] Compound A is an allosteric inhibitor of Abl1 that targets the myristoyl binding site and can be used to treat diseases mediated by Bcr-Abl kinase and its mutants, such as chronic myeloid leukemia. The compound was first disclosed in International Patent Publication No. WO 2018 / 133827 A1, but no crystals of Compound A were disclosed. The applicant of WO 2018 / 133827 A1 is Shenzhen TargetRx Inc. The Chinese application CN 201880000986.9 corresponding to WO 2018 / 133827 A1 was published on August 27, 2019 under registration number CN 108602800 B. In addition, WO 2018 / 133827 A1 has corresponding U.S. application US 16 / 479,299, European application EP 18741306.7, and Japanese application JP 2019-560440, the contents of each of the above applications being incorporated herein by reference in their entirety. Summary of the Invention
[0004] In one aspect, the present disclosure provides various crystalline forms of the free base of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Compound A). to provide.
[0005] In one embodiment, the disclosure provides crystalline Form I of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form I of Compound A).
[0006] In another embodiment, the present disclosure provides crystalline Form II of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form II of Compound A).
[0007] In another embodiment, the present disclosure provides crystalline Form III of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form III of Compound A).
[0008] In another embodiment, the disclosure provides crystalline Form IV of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form IV of Compound A).
[0009] In another embodiment, the present disclosure provides Form V crystals of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Form V crystals of Compound A).
[0010] In another embodiment, the present disclosure provides Form VI crystals of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Form VI crystals of Compound A).
[0011] In another embodiment, the present disclosure provides Form VII crystals of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Form VII crystals of Compound A).
[0012] In another embodiment, the present disclosure provides crystalline Form VIII of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form VIII of Compound A).
[0013] In another embodiment, the present disclosure provides Form IX crystals of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Form IX crystals of Compound A).
[0014] In another embodiment, the present disclosure provides crystalline Form X of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (crystalline Form X of Compound A).
[0015] In another embodiment, the disclosure provides Form XI crystals of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (Form XI crystals of Compound A).
[0016] In another embodiment, the present disclosure provides various crystalline forms of a salt of Compound A.
[0017] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide hydrochloride and Form I crystalline form of the hydrochloride salt (Form I crystalline form of the hydrochloride salt of Compound A).
[0018] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide benzenesulfonate and Form I crystals of the benzenesulfonate salt (Form I crystals of the benzenesulfonate salt of Compound A).
[0019] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide p-toluenesulfonate and Form I crystals of the p-toluenesulfonate salt (Form I crystals of the p-toluenesulfonate salt of Compound A).
[0020] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide p-toluenesulfonate and Form II crystals of the p-toluenesulfonate salt (Form II crystals of the p-toluenesulfonate salt of Compound A).
[0021] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide mesylate and Form I crystalline form of the mesylate salt (Form I crystalline form of the mesylate salt of Compound A).
[0022] In one embodiment, the present disclosure provides (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide hydrobromide and Form I crystals of the hydrobromide salt (Form I crystals of the hydrobromide salt of Compound A).
[0023] In another aspect, the present disclosure provides a method for preparing a crystalline Form VI of Compound A, comprising converting a crystalline Form VII of Compound A to a crystalline Form VI of Compound A.
[0024] In one embodiment, the disclosure provides a method of preparing a compound of formula (A): [ka]
[0025] wherein X is a halogen; preferably, I or Br; more preferably, I;
[0026] The method comprises reacting a compound of formula (B), its boronic acid hydrolysis product, or a mixture thereof, with 2-halopyrazine in the presence of a palladium catalyst and a base in DMSO or DMF.
[0027] In another embodiment, the disclosure provides a method of preparing a compound of formula (A): [ka]
[0028] wherein X is a halogen; preferably, I or Br; more preferably, I;
[0029] The method comprises reacting a compound of formula (B), its boronic acid hydrolysis product, or a mixture thereof, with a 2-halopyrazine in the presence of a palladium catalyst and a quaternary ammonium salt.
[0030] In another aspect, the present disclosure provides a pharmaceutical composition comprising: (i) a crystalline free base form of Compound A or a crystalline pharma- ceutically acceptable salt thereof; (ii) a diluent; (iii) a disintegrant; (iv) a glidant; and (v) a lubricant.
[0031] In another aspect, the present disclosure provides a pharmaceutical composition comprising: (i) a compound of formula (A); (ii) a diluent; (iii) a disintegrant; (iv) a glidant; and (v) a lubricant, wherein the glidant is in an amount of 1% to 5% by weight, preferably 2% to 4% by weight, or preferably about 3% by weight of the total weight of the pharmaceutical composition.
[0032] In another embodiment, the disclosure provides the use of crystals of the above type in the manufacture of a medicament for treating and / or preventing a disease caused by Bcr-Abl.
[0033] In another embodiment, the present disclosure provides a crystal of the above type for use in the treatment and / or prevention of a Bcr-Abl mediated disease.
[0034] In another embodiment, the disclosure provides a method of treating and / or preventing a Bcr-Abl mediated disease in a subject, comprising administering to said subject crystals of the above-mentioned type.
[0035] In another embodiment, the above Bcr-Abl-driven disease includes solid tumors, sarcomas, acute lymphocytic leukemia, acute myeloid leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, gastrointestinal stromal tumors, thyroid cancer, gastric cancer, rectal cancer, multiple myeloma, neoplasia, and other proliferative diseases; or the Bcr-Abl1-driven disease is metastatic invasive cancer, viral infection, or CNS disorder. [Brief description of the drawings]
[0036] [Figure 1] FIG. 1 shows the XRPD pattern of the Type I crystal of Compound A.
[0037] [Diagram 2] FIG. 2 shows the DVS curve of the type I crystal of Compound A.
[0038] [Diagram 3] FIG. 3 shows a comparison of the XRPD patterns of crystalline Form I of Compound A before and after DVS testing.
[0039] [Figure 4] FIG. 4 shows the XRPD pattern of the crystal form II of Compound A.
[0040] [Diagram 5] FIG. 5 shows the XRPD pattern of the type III crystal of Compound A.
[0041] [Figure 6] FIG. 6 shows the XRPD pattern of crystalline form IV of Compound A.
[0042] [Figure 7] FIG. 7 shows the XRPD pattern of crystalline form V of Compound A.
[0043] [Figure 8] FIG. 8 shows the XRPD pattern of crystalline form VI of Compound A.
[0044] [Figure 9] FIG. 9 shows the 1H NMR spectrum of the VI type crystal of Compound A.
[0045] [Figure 10] FIG. 10 shows the 13C NMR spectrum of the VI type crystal of Compound A.
[0046] [Figure 11] FIG. 11 shows the NMR DEPT spectrum of the VI type crystal of Compound A.
[0047] [Figure 12] FIG. 12 shows the NMR 19F-NMR spectrum of the VI type crystal of Compound A.
[0048] [Figure 13] FIG. 13 shows the NMR HF NOESY spectrum of the VI type crystal of Compound A.
[0049] [Figure 14] FIG. 14 shows the NMR HSQC spectrum of the VI type crystal of Compound A.
[0050] [Figure 15] FIG. 15 shows the NMR HMBC spectrum of the VI type crystal of Compound A.
[0051] [Figure 16] FIG. 16 shows the NMR COSY spectrum of the VI type crystal of Compound A.
[0052] [Figure 17] FIG. 17 shows the NMR NOESY spectrum of the VI type crystal of Compound A.
[0053] [Figure 18] FIG. 18 shows the mass spectrum of the VI type crystal of Compound A.
[0054] [Figure 19] FIG. 19 shows the UV spectrum of the VI type crystal of Compound A.
[0055] [Figure 20] FIG. 20 shows a DSC curve of the VI type crystal of Compound A.
[0056] [Figure 21] FIG. 21 shows a TGA curve of the VI type crystal of Compound A.
[0057] [Figure 22] FIG. 22 shows a DVS curve of the VI type crystal of Compound A.
[0058] [Figure 23] FIG. 23 shows an IR spectrum of the VI type crystal of Compound A.
[0059] [Figure 24] FIG. 24 shows the XRPD pattern of the Form VII crystal of Compound A.
[0060] [Diagram 25] FIG. 25 shows the XRPD pattern of crystalline form VIII of Compound A.
[0061] [Figure 26] FIG. 26 shows the XRPD pattern of crystalline form IX of Compound A.
[0062] [Figure 27] FIG. 27 shows the XRPD pattern of crystalline form X of Compound A.
[0063] [Figure 28] FIG. 28 shows the XRPD pattern of crystalline Form XI of Compound A.
[0064] [Figure 29] FIG. 29 shows the XRPD patterns for the stability study of crystalline Form I of Compound A.
[0065] [Diagram 30] FIG. 30 shows the XRPD patterns of crystalline Forms III, VI, and VII of Compound A before and after milling.
[0066] [Diagram 31] FIG. 31 shows the XRPD pattern of Form I crystals of Compound A hydrochloride.
[0067] [Diagram 32] FIG. 32 shows a DVS curve of type I crystals of Compound A hydrochloride.
[0068] [Diagram 33] FIG. 33 shows a comparison of XRPD patterns of crystalline Form I of the hydrochloride salt of Compound A before and after DVS testing.
[0069] [Diagram 34] FIG. 34 shows an XRPD pattern of Form I crystals of the benzenesulfonate salt of Compound A.
[0070] [Diagram 35] FIG. 35 shows a DVS curve of the benzenesulfonate crystal of Compound A.
[0071] [Diagram 36] FIG. 36 shows a comparison of XRPD patterns of crystalline Form I of the benzenesulfonate salt of Compound A before and after DVS testing.
[0072] [Figure 37]FIG. 37 shows an XRPD pattern of Form I crystals of the p-toluenesulfonate salt of Compound A.
[0073] [Figure 38] FIG. 38 shows a DVS curve of type I crystals of p-toluenesulfonate of Compound A.
[0074] [Figure 39] FIG. 39 shows a comparison of the XRPD patterns of crystalline Form I of the p-toluenesulfonate salt of Compound A before and after DVS.
[0075] [Diagram 40] FIG. 40 shows an XRPD pattern of crystal Form II of the p-toluenesulfonate salt of Compound A.
[0076] [Diagram 41] FIG. 41 shows the XRPD pattern of Form I crystals of the mesylate salt of Compound A.
[0077] [Diagram 42] FIG. 42 shows a DVS curve of type I crystals of the mesylate salt of Compound A.
[0078] [Diagram 43] FIG. 43 shows a comparison of XRPD patterns of crystalline Form I of Compound A mesylate salt before and after DVS testing.
[0079] [Diagram 44] FIG. 44 shows the XRPD pattern of crystalline Form I of the hydrobromide salt of Compound A.
[0080] [Diagram 45] FIG. 45 shows a DVS curve of type I crystals of the hydrobromide salt of Compound A.
[0081] [Figure 46] FIG. 46 shows a comparison of XRPD patterns of crystalline Form I of the hydrobromide salt of Compound A before and after DVS testing.
[0082] [Figure 47] FIG. 47 shows the XRPD patterns for a stability study of crystalline Form I of p-toluenesulfonate salt of Compound A.
[0083] [Figure 48] FIG. 48 is an XRPD pattern showing the crystal form change of Form I crystal of Compound A dissolved in SGF.
[0084] [Figure 49] FIG. 49 is an XRPD pattern showing the crystal form change of the Type I crystal of Compound A dissolved in FaSSIF.
[0085] [Figure 50] FIG. 50 is an XRPD pattern showing the crystal form change of Form I crystal of Compound A dissolved in FeSSIF.
[0086] [Figure 51] FIG. 51 is an XRPD pattern showing the crystal form change of Compound A p-toluenesulfonate dissolved in SGF.
[0087] [Figure 52] FIG. 52 is an XRPD pattern showing the crystal form change of Type I crystal of p-toluenesulfonate salt of Compound A dissolved in FaSSIF.
[0088] [Diagram 53] FIG. 53 is an XRPD pattern showing the crystal form change of Form I crystal of p-toluenesulfonate salt of Compound A dissolved in FeSSIF.
[0089] [Figure 54] FIG. 54 shows the crystal structure of compound A.
[0090] [Figure 55] FIG. 55 shows the XRPD patterns for the stability study of crystalline Form VI of Compound A.
[0091] Detailed Description of the Invention The present disclosure may be more readily understood by reference to the following detailed description of the embodiments of the present disclosure and the examples contained herein. It should be understood that the terms used herein are intended only to describe specific embodiments and are not intended to be limiting. It should also be understood that the terms used herein are to be given their ordinary meanings known in the relevant technical field unless clearly defined by the context.
[0092] As used herein, the singular forms "a," "an," and "the" include plural references unless otherwise specified. For example, the term "a" compound includes one or more compounds.
[0093] The term "about" means having a value that falls within the standard error of the accepted mean when considered by one of ordinary skill in the art. For example, "about" means ±10% of the stated amount, or ±5% of the stated amount.
[0094] As used herein, the term "substantially" means taking into account typical variations of a particular method and standard error of measurement. For example, with respect to X-ray powder diffraction peak positions, the term "substantially" means taking into account typical variations in peak positions and intensities. Those skilled in the art will recognize that peak positions (2θ) will exhibit some variation, typically up to ±0.2°. Additionally, those skilled in the art will recognize that relative peak intensities will account for instrument-to-instrument variations, as well as variations due to crystallinity, preferred orientation, surface of the sample being tested, and other factors known to those skilled in the art. Similarly, 1 H, 13 C and 19 The NMR spectrum of F (ppm) shows variations, typically up to ±0.2 ppm.
[0095] As used herein, the terms "crystal" and "crystal form" refer to a solid composed of molecules with a regular repeating sequence. Crystal forms may differ in thermodynamic stability, physical parameters, X-ray structure, and preparation process.
[0096] The term "amorphous" refers to a solid composed of molecules with a disordered arrangement.
[0097] As used herein, the term "solvate" refers to a type of crystal that has a stoichiometric or non-stoichiometric amount of a solvent (e.g., water, methanol, ethyl acetate, etc., or mixtures thereof) within the crystal lattice through non-covalent intermolecular bonds. The term "hydrate" refers to a solvate in which the solvent is water.
[0098] As used herein, the term "anhydrous" refers to a crystalline form that contains less than about 1% (w / w) adsorbed water as measured by standard methods such as Karl Fisher analysis.
[0099] The compound (R)—N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide, referred to herein as Compound A, or the free base of Compound A, has the formula: [ka] As shown in the figure.
[0100] The present disclosure relates to various crystalline forms of Compound A, such as "crystalline form I of Compound A", "crystalline form II of Compound A", "crystalline form III of Compound A", "crystalline form IV of Compound A", "crystalline form V of Compound A", "crystalline form VI of Compound A", "crystalline form VII of Compound A", "crystalline form VIII of Compound A", "crystalline form IX of Compound A", "crystalline form X of Compound A", and "crystalline form XI of Compound A". In some embodiments, the crystalline forms of the compound may be in the form of a solvate, a hydrate, or a non-solvate.
[0101] In one embodiment, the disclosure provides crystalline Form I of Compound A, which is an ethanol solvate, wherein the molar ratio of ethanol to free base is 1:2.
[0102] In another embodiment, the X-ray powder diffraction pattern of the Form I crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 18.3±0.2 and 24.4±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 9.6±0.2, 19.3±0.2, 21.8±0.2, 22.5±0.2 and 24.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 10.7±0.2, 12.2±0.2, 16.2±0.2, 22.8±0.2, 23.4±0.2 and 27.8±0.2.
[0103] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 1]
[0104] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.1. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0105] In another embodiment, the Form I crystal has an endothermic peak at 173±2° C. in differential scanning calorimetry.
[0106] In another embodiment, the Form I crystal has a weight loss of about 5.1% before 200° C. in thermogravimetric analysis.
[0107] Compound A type II crystal In one embodiment, the disclosure provides crystalline Form II of Compound A, which is an acetonitrile solvate, wherein the molar ratio of acetonitrile to free base is 1:5.
[0108] In another embodiment, the X-ray powder diffraction pattern of the II crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 11.0±0.2, 11.6±0.2, 13.0±0.2, 17.1±0.2, 19.6±0.2, 19.8±0.2 and 22.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 5.8±0.2, 6.4±0.2, 10.8±0.2, 14.9±0.2, 15.3±0.2, 16.4±0.2, 19.3±0.2, 20.6±0.2, 23.3±0.2, 25.1±0.2 and 26.9±0.2.
[0109] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 2]
[0110] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.2. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0111] In another embodiment, the Form II crystal has an endothermic peak at 115±2° C. in differential scanning calorimetry analysis.
[0112] In another embodiment, the Form II crystal has a weight loss of about 1.9% before 200° C. in thermogravimetric analysis.
[0113] In one embodiment, the present disclosure provides crystalline Form III of Compound A, which is a hydrate, wherein the molar ratio of water to free base is 1:1.
[0114] In another embodiment, the X-ray powder diffraction pattern of the III crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 12.4±0.2, 14.2±0.2, 20.0±0.2 and 21.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 7.0±0.2, 9.3±0.2, 13.9±0.2 and 24.5±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 15.3±0.2, 20.6±0.2, 23.4±0.2, 27.5±0.2, 28.3±0.2 and 28.8±0.2.
[0115] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 3]
[0116] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.3. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0117] In another embodiment, the Form III crystal has an endothermic peak at 173±2° C. in differential scanning calorimetry analysis.
[0118] In another embodiment, the Form III crystal has a weight loss of about 3.5% at 200° C. in thermogravimetric analysis.
[0119] Compound A type IV crystal In one embodiment, the disclosure provides crystalline Form IV of Compound A, which is a methanol solvate, wherein the molar ratio of methanol to free base is 1:2.
[0120] In another embodiment, the X-ray powder diffraction pattern of the IV crystal using CuKα radiation contains at least characteristic peaks at °2θ: 9.7±0.2, 22.5±0.2, and 24.4±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 6.2±0.2, 12.9±0.2, 18.4±0.2, 21.8±0.2, 23.2±0.2, and 24.8±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 6.4±0.2, 10.8±0.2, 12.3±0.2, 16.0±0.2, 19.2±0.2, 21.1±0.2, and 27.9±0.2.
[0121] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 4]
[0122] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.4. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0123] In another embodiment, the Form IV crystal has endothermic peaks at 176±2° C. and 251±2° C. in differential scanning calorimetry analysis.
[0124] In another embodiment, the Form IV crystal has a weight loss of about 3.7% before 200° C. in thermogravimetric analysis.
[0125] In another embodiment, the Form IV crystal has the following unit cell parameters: [Table 5]
[0126] Compound A V-type crystal In one embodiment, the disclosure provides crystalline Form V of Compound A, which is an isobutanol solvate, wherein the molar ratio of isobutanol to free base is 1:6.
[0127] In another embodiment, the X-ray powder diffraction pattern of the V-type crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 9.4±0.2, 18.1±0.2, 18.9±0.2, 21.3±0.2 and 23.6±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 24.3±0.2 and 26.8±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 9.9±0.2, 11.8±0.2, 15.6±0.2, 15.9±0.2, 17.6±0.2, 18.4±0.2, 19.1±0.2, 19.8±0.2, 21.8±0.2 and 23.2±0.2.
[0128] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 6]
[0129] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.5. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0130] In another embodiment, the Type V crystal has an endothermic peak at 173±2° C. in differential scanning calorimetry analysis.
[0131] In another embodiment, the Type V crystals have a weight loss of about 6.5% before 200° C. in thermogravimetric analysis.
[0132] Compound A VI type crystal In one embodiment, the present disclosure provides crystalline Form VI of Compound A, which is anhydrous.
[0133] In another embodiment, the X-ray powder diffraction pattern of the VI crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 11.9±0.2, 20.5±0.2, 23.1±0.2, 23.9±0.2 and 24.8±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 9.7±0.2, 16.1±0.2, 19.3±0.2 and 21.2±0.2. In another embodiment, said X-ray powder diffraction pattern further comprises characteristic peaks located at degrees 2θ: 5.9±0.2, 11.0±0.2, 12.8±0.2, 14.7±0.2, 16.6±0.2, 17.8±0.2, 18.2±0.2, 18.6±0.2, 20.1±0.2, 22.0±0.2, 22.6±0.2, 26.2±0.2 and 29.0±0.2.
[0134] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 7]
[0135] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.6. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0136] In another embodiment, the Form VI crystal has an endothermic peak in differential scanning calorimetry analysis at 175±2° C. In another embodiment, the Form VI crystal has a DSC curve substantially as shown in FIG.
[0137] In another embodiment, the Form VI crystal exhibits substantially no weight loss in thermogravimetric analysis before 200° C. In another embodiment, the Form VI crystal has a TGA curve substantially as shown in FIG.
[0138] In another embodiment, the VI crystal has a cm -1 23. In another embodiment, the Form VI crystal has an infrared absorption spectrum substantially as shown in FIG.
[0139]
[0139] In another embodiment, the Form VI crystal has absorption peaks in the UV spectrum at nm: 201±2, 263±2, and 306±2. In another embodiment, the Form VI crystal has a UV spectrum substantially as shown in FIG.
[0140] Compound A VII type crystal In one embodiment, the present disclosure provides crystalline Form VII of Compound A which is a hydrate, the molar ratio of water to free base being 1:1.
[0141] In another embodiment, the X-ray powder diffraction pattern of the VII crystal obtained using CuKα radiation contains at least characteristic peaks at °2θ: 11.7±0.2, 16.9±0.2, 18.3±0.2, 20.9±0.2, 21.7±0.2, 23.2±0.2, 23.8±0.2 and 27.1±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 13.4±0.2, 16.0±0.2, 20.7±0.2 and 22.2±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 13.2±0.2, 19.6±0.2, 21.3±0.2, 25.7±0.2 and 30.9±0.2.
[0142] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 8]
[0143] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at 2θ in Table 3.7. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0144] In another embodiment, the Form VII crystal has an endothermic peak at 174±2° C. in differential scanning calorimetry analysis.
[0145] In another embodiment, the Form VII crystal has a weight loss of about 3.4% before 200° C. in thermogravimetric analysis.
[0146] Compound A VIII type crystal In one embodiment, the present disclosure is crystalline Form VIII of Compound A, which is an ethanol solvate, wherein the molar ratio of ethanol to free base is 2:5.
[0147] In another embodiment, the X-ray powder diffraction pattern of the VIII crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 9.6±0.2, 12.7±0.2, 18.3±0.2, 19.1±0.2, 22.8±0.2 and 24.3±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 10.7±0.2, 12.1±0.2, 19.4±0.2, 21.8±0.2, 22.5±0.2, 24.7±0.2 and 27.6±0.2.
[0148] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 9]
[0149] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.8. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0150] Compound A IX type crystal In one embodiment, the disclosure provides crystalline Form IX of Compound A, which is a solvate of ethanol, isopropanol, and tetrahydrofuran, wherein the molar ratio of ethanol to free base is 1:2, the molar ratio of isopropanol to free base is 1:3, and the molar ratio of tetrahydrofuran to free base is 0.06:1.
[0151] In another embodiment, the X-ray powder diffraction pattern of the IX crystal obtained using CuKα radiation contains at least characteristic peaks at °2θ: 9.6±0.2, 18.2±0.2, and 22.1±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 6.1±0.2, 12.1±0.2, 12.4±0.2, 19.0±0.2, 19.3±0.2, 21.5±0.2, 24.4±0.2, and 24.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 10.5±0.2, 16.1±0.2, 20.6±0.2, 21.2±0.2, 23.6±0.2, 26.9±0.2, 27.7±0.2, and 28.4±0.2.
[0152] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 10]
[0153] In another embodiment, the X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.9. In another embodiment, the X-ray powder diffraction pattern is substantially as shown in FIG.
[0154] In another embodiment, the Form IX crystal has an endothermic peak at 174±2° C. in differential scanning calorimetry analysis.
[0155] In another embodiment, the Form IX crystal has a weight loss of about 5.8% before 200° C. in thermogravimetric analysis.
[0156] X-type crystal of compound A In one embodiment, the disclosure provides crystalline Form X of Compound A, which is a tetrahydrofuran solvate, of which the molar ratio of tetrahydrofuran to free base is 1:12.
[0157] In another embodiment, the X-ray powder diffraction pattern of the X-type crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 7.0±0.2, 9.3±0.2, 12.3±0.2, 14.2±0.2, 16.3±0.2, 18.8±0.2, 19.9±0.2, 21.4±0.2 and 23.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 15.4±0.2, 19.2±0.2, 19.5±0.2, 22.2±0.2, 23.4±0.2, 24.8±0.2, 25.8±0.2, 26.2±0.2, 26.7±0.2, 28.8±0.2 and 29.2±0.2.
[0158] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 11]
[0159] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values of Table 3.10. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0160] In another embodiment, the Type X crystal has an endothermic peak at 173±2° C. in differential scanning calorimetry analysis.
[0161] In another embodiment, the Form X crystal has a weight loss of about 3.6% before 200° C. in thermogravimetric analysis.
[0162] Compound A XI type crystal In one embodiment, the disclosure provides crystalline Form XI of Compound A, which is an acetonitrile solvate, wherein the molar ratio of acetonitrile to free base is 2:5.
[0163] In another embodiment, the X-ray powder diffraction pattern of the XI crystal obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 9.7±0.2, 17.9±0.2, 19.5±0.2, 24.2±0.2 and 24.8±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 7.6±0.2, 12.7±0.2, 13.2±0.2, 18.7±0.2, 18.9±0.2, 22.4±0.2 and 25.6±0.2. In another embodiment, said X-ray powder diffraction pattern further comprises characteristic peaks located at degrees 2θ: 14.6±0.2, 16.7±0.2, 20.2±0.2, 20.7±0.2, 21.0±0.2, 21.3±0.2, 26.0±0.2 and 29.9±0.2.
[0164] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 12]
[0165] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values of Table 3.11. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0166] In another embodiment, the Form XI crystal has an endothermic peak at 174±2° C. in differential scanning calorimetry analysis.
[0167] In another embodiment, the Form XI crystal has a weight loss of about 3.9% before 200° C. in thermogravimetric analysis.
[0168] Salts of compound A and their crystal forms The present disclosure relates to various salts of Compound A, such as the hydrochloride, benzenesulfonate, p-toluenesulfonate, mesylate, and hydrobromide salts.
[0169] The present disclosure also relates to crystalline forms of various salts of Compound A, such as "crystalline form I of the hydrochloride salt of Compound A," "crystalline form I of the benzenesulfonate salt of Compound A," "crystalline form I of the p-toluenesulfonate salt of Compound A," "crystalline form II of the p-toluenesulfonate salt of Compound A," "crystalline form I of the mesylate salt of Compound A," and "crystalline form I of the hydrobromide salt of Compound A."
[0170] Form I crystal of the hydrochloride salt of Compound A In one embodiment, the disclosure provides crystalline Form I of the hydrochloride salt of Compound A. In another embodiment, crystalline Form I of the hydrochloride salt of Compound A is anhydrous.
[0171] In another embodiment, the X-ray powder diffraction pattern of the Form I crystal of the hydrochloride salt obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 6.5±0.2, 13.8±0.2, 18.7±0.2, and 23.3±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 11.3±0.2, 15.7±0.2, 16.4±0.2, 21.9±0.2, 22.7±0.2, 24.2±0.2, and 28.6±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 16.8±0.2, 19.7±0.2, 20.8±0.2, 21.3±0.2, 25.2±0.2, and 35.0±0.2.
[0172] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 13]
[0173] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.1. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0174] In another embodiment, the Form I crystalline form of the hydrochloride salt has an endothermic peak at 229±2° C. in differential scanning calorimetry analysis.
[0175] In another embodiment, crystalline Form I of the hydrochloride salt has a weight loss of about 0.7% at 175° C. in thermogravimetric analysis.
[0176] Form I crystal of benzenesulfonate of compound A In one embodiment, the disclosure provides crystalline Form I of the benzenesulfonate salt of Compound A. In another embodiment, the crystalline Form I of the benzenesulfonate salt is anhydrous.
[0177] In another embodiment, the X-ray powder diffraction pattern of the benzenesulfonate salt obtained using CuKα radiation contains at least characteristic peaks at °2θ: 7.6±0.2, 10.2±0.2, and 22.8±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 16.4±0.2, 19.1±0.2, 19.9±0.2, 21.3±0.2, 21.9±0.2, and 23.3±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks at °2θ: 20.5±0.2, 21.6±0.2, and 25.0±0.2.
[0178] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 14]
[0179] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.2. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0180] In another embodiment, the Form I crystals of the benzenesulfonate salt have an endothermic peak at 253±2° C. in differential scanning calorimetry analysis.
[0181] In another embodiment, the Form I crystals of the benzenesulfonate salt have a weight loss of about 0.5% at 200° C. in thermogravimetric analysis.
[0182] Form I crystal of p-toluenesulfonate of compound A In one embodiment, the present disclosure provides crystalline Form I of the p-toluenesulfonate salt of Compound A. In another embodiment, the crystalline Form I of the p-toluenesulfonate salt is anhydrous.
[0183] In another embodiment, the X-ray powder diffraction pattern of the Form I crystal of the p-toluenesulfonate salt obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 7.4±0.2, 10.2±0.2, 21.3±0.2, and 21.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 27.9±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 14.9±0.2, 16.3±0.2, 19.2±0.2, and 23.0±0.2.
[0184] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 15]
[0185] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at 2θ in Table 3.3. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0186] In another embodiment, the Form I crystals of the p-toluenesulfonate salt have an endothermic peak at 236±2° C. in differential scanning calorimetry analysis.
[0187] In another embodiment, the Form I crystal of the p-toluenesulfonate salt has a weight loss of about 0.1% at 200° C. in thermogravimetric analysis.
[0188] Form II crystal of p-toluenesulfonate of compound A In one embodiment, the present disclosure provides a crystalline Form II of p-toluenesulfonate salt of Compound A. In another embodiment, the crystalline Form II of p-toluenesulfonate salt is anhydrous.
[0189] In another embodiment, the X-ray powder diffraction pattern of the Form II crystals of the p-toluenesulfonate salt obtained using CuKα radiation includes at least characteristic peaks located at °2θ: 6.4±0.2, 7.4±0.2, 10.2±0.2, 16.3±0.2, 21.3±0.2 and 21.8±0.2.
[0190] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 16]
[0191] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.4. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0192] In another embodiment, the Form II crystals of the p-toluenesulfonate salt have an endothermic peak at 234±2° C. in differential scanning calorimetry analysis.
[0193] In another embodiment, the Form II crystals of the p-toluenesulfonate salt have a weight loss of about 0.2% at 200° C. in thermogravimetric analysis.
[0194] Form I crystal of mesylate of compound A In one embodiment, the present disclosure provides crystalline Form I of a mesylate salt of Compound A. In another embodiment, the crystalline Form I of the mesylate salt is anhydrous.
[0195] In another embodiment, the X-ray powder diffraction pattern of Form I crystals of the mesylate salt obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 19.7±0.2 and 23.7±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 4.7±0.2, 16.4±0.2, 18.7±0.2, 19.2±0.2, 22.3±0.2 and 22.7±0.2. In another embodiment, the X-ray powder diffraction pattern further contains characteristic peaks located at °2θ: 20.1±0.2, 28.1±0.2 and 37.1±0.2.
[0196] In another embodiment, the X-ray powder diffraction pattern has the characteristic peaks: [Table 17]
[0197] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.5. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0198] In another embodiment, the Form I crystalline mesylate salt has an endothermic peak at 206±2° C. in differential scanning calorimetry analysis.
[0199] In another embodiment, the Form I crystalline mesylate salt has a weight loss of about 0.7% at 200° C. in thermogravimetric analysis.
[0200] Form I crystal of the hydrobromide salt of compound A In one embodiment, the disclosure provides crystalline Form I of the hydrobromide salt of Compound A. In another embodiment, said crystalline Form I of the hydrobromide salt is anhydrous.
[0201] In another embodiment, the hydrobromide salt is obtained using CuKα radiation. has at least characteristic peaks located at °2θ: 6.4±0.2, 13.5±0.2, 20.6±0.2, 21.1±0.2, 23.8±0.2, 24.0±0.2 and 26.1±0.2. In another embodiment, said X-ray powder diffraction pattern further comprises characteristic peaks located at °2θ: 13.0±0.2 and 28.5±0.2.
[0202] In another embodiment, the X-ray powder diffraction pattern has the following characteristic peaks: [Table 18]
[0203] In another embodiment, said X-ray powder diffraction pattern comprises one or more peaks at the 2θ values in Table 3.6. In another embodiment, said X-ray powder diffraction pattern is substantially as shown in FIG.
[0204] In another embodiment, the Form I crystalline form of the hydrobromide salt has an endothermic peak at 251±2° C. in differential scanning calorimetry analysis.
[0205] In another embodiment, the Form I crystalline form of the hydrobromide salt has a weight loss of about 0.6% at 200° C. in thermogravimetric analysis.
[0206] Method for preparing compound A and its VI crystal form The present disclosure relates to a method for preparing high purity compound A and its crystalline form VI on a kilogram scale, see Scheme 1.
[0207] Scheme 1 [ka]
[0208] Step 1: Compound D is subjected to a substitution reaction with 3-(R)-fluoropyrrolidine hydrochloride in the presence of a base, preferably an inorganic base. Step 2: Compound C is reacted with bis(pinacolato)diboron in the presence of a specific palladium catalyst and acetate to form intermediate compound B or its boronic acid hydrolyzate or a mixture thereof, which is reacted with 2-halopyrazine in the presence of a palladium catalyst and base to form compound A. Preferably, the product is recrystallized to obtain type VII crystals of compound A. Step 3: Type VII crystals of compound A are converted to type VI crystals of compound A.
[0209] Process 1 [ka]
[0210] In step 1, compound D is reacted with 3-(R)-fluoropyrrolidine hydrochloride in the presence of a base to produce compound C.
[0211] In a specific embodiment, the reaction is carried out in an aprotic solvent in the presence of a base. In another specific embodiment, the base is an inorganic base, preferably sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium carbonate, potassium carbonate, cesium carbonate, sodium bicarbonate or potassium bicarbonate; preferably sodium carbonate, potassium carbonate or cesium carbonate; preferably sodium carbonate.
[0212] In another specific embodiment, the aprotic solvent is selected from DCM, DCE, ethyl acetate, methyl acetate, isopropyl acetate, n-hexane, n-heptane, petroleum ether, acetone, acetonitrile, toluene, methyl tert-butyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, DMF, DMA or DMSO; preferably, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, DMF or DMSO; preferably, DMSO.
[0213] According to another specific embodiment, the reaction is carried out at a temperature between 50° C. and solvent reflux, preferably 50-90° C., or more preferably 70±10° C., for at least 1 hour, preferably at least 20 hours.
[0214] In another specific embodiment, the molar ratio of compound D to 3-(R)-fluoropyrrolidine hydrochloride is 0.8-1.2:1, preferably 1:1.
[0215] In another specific embodiment, the amount of base is 2 to 3 times the amount of compound D, alternatively 2.2 times.
[0216] Process 2-1 [ka]
[0217] Process 2-2 [ka]
[0218] In step 2, compound C is reacted with bis(pinacolato)diboron in the presence of a palladium catalyst Pd(dppf)Cl2 and acetate to produce intermediate compound B and its boronic acid hydrolysis product or a mixture thereof (step 2-1), which is reacted with 2-halopyrazine in the presence of a palladium catalyst and a base to produce compound A (step 2-2).
[0219] In a specific embodiment of step 2-1, the reaction is as follows: [ka]
[0220] In another specific embodiment of step 2-1, the reaction comprises reacting the compound of formula (C) with bis(pinacolato)diboron in the presence of palladium catalyst Pd(dppf)Cl2 and acetate in a solvent, where the solvent is selected from DMSO, DCM, DCE, ethyl acetate, methyl acetate, isopropyl acetate, acetone, acetonitrile, methyl tert-butyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, DMF or DMA; preferably, DMSO, 2-methyltetrahydrofuran, ethylene glycol monomethyl ether or DMF; preferably, DMSO.
[0221] In certain embodiments of step 2-1, the acetate is selected from potassium acetate, sodium acetate, or cesium acetate; preferably, it is potassium acetate.
[0222] In a specific embodiment of step 2-1, the amount of acetate is 2 to 5 times that of compound C; preferably 2.5 times.
[0223] In a specific embodiment of step 2-1, the amount of bis(pinacolato)diboron is 3 to 6 times that of compound C; preferably, 3 times.
[0224] In a specific embodiment of Step 2-1, the amount of the catalyst is 0.01 to 0.1 times, preferably 0.05 times, that of compound C.
[0225] In certain embodiments of step 2-1, the reaction is carried out at a temperature of from 60° C. to solvent reflux, preferably 60-100° C., or more preferably 80±10° C.; preferably for a reaction period of at least 1 hour, preferably at least 2 hours.
[0226] In a specific embodiment of step 2-2, the reaction is as follows: [ka]
[0227] wherein X is a halogen; preferably, I or Br; more preferably, I.
[0228] In another specific embodiment of step 2-2, the reaction comprises reacting a compound of formula (B), its boronic acid hydrolysate, or a mixture thereof with 2-halopyrazine in the presence of a palladium catalyst and a base in DMSO or DMF.
[0229] In another specific embodiment of step 2-2, DMSO or DMF contains water in a volume ratio of 0.01-0.5:1; preferably 0.05-0.2:1, preferably 0.067:1, 0.1:1 or 0.2:1.
[0230] In another specific embodiment of step 2-2, the base is selected from sodium phosphate, potassium phosphate, sodium carbonate, potassium carbonate, cesium carbonate, a quaternary ammonium salt, NaF, KF, CsF, sodium bicarbonate, potassium bicarbonate, dibasic sodium phosphate, or dibasic potassium phosphate.
[0231] In another specific embodiment of step 2-2, the quaternary ammonium salt is selected from organic quaternary ammonium salts including tetrabutylammonium fluoride, tetrabutylammonium bromide, tetraethylammonium fluoride, tetraethylammonium bromide, tetramethylammonium fluoride, tetramethylammonium bromide, or tetramethylammonium chloride; preferably, tetrabutylammonium fluoride.
[0232] In another specific embodiment of step 2-2, the base is selected from sodium phosphate, potassium phosphate, sodium carbonate, potassium carbonate, cesium carbonate, tetrabutylammonium fluoride, NaF, KF, and CsF.
[0233] In another specific embodiment of step 2-2, the palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, palladium acetate, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium, palladium dichloride or bis(triphenylphosphine)palladium dichloride; preferably, 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or bis(triphenylphosphine)palladium dichloride; preferably, 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride.
[0234] In another specific embodiment of step 2-2, the molar ratio of 2-halopyrazine to compound B or its boronic acid hydrolysis product or a mixture thereof is 0.8-1.5:1; preferably, 1.2:1.
[0235] In another specific embodiment of step 2-2, the amount of base is 1 to 3.5 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof; preferably 1.2 to 2.7 times; preferably 1.2 times, 1.5 times, 1.8 times, 2.0 times, 2.1 times, 2.2 times, 2.4 times or 2.7 times.
[0236] In another specific embodiment of step 2-2, the amount of the palladium catalyst is 0.005 to 0.1 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof; preferably, 0.01 to 0.05 times; preferably, 0.01 times, 0.02 times, 0.03 times, 0.04 times, or 0.05 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof.
[0237] In another specific embodiment of step 2-2, the reaction is carried out at a temperature ranging from room temperature to solvent reflux, preferably 30-80° C., or more preferably 30±5° C., 50±5° C., 65±5° C. or 80±5° C.; preferably for a reaction time of at least 1 hour, preferably at least 3 hours.
[0238] In a specific embodiment of step 2-2, the reaction is as follows: [ka]
[0239] wherein X is a halogen; preferably, I or Br; more preferably, I.
[0240] In another specific embodiment of Step 2-2, the method includes reacting a compound represented by Formula (B), its boronic acid hydrolysis product, or a mixture thereof, with a 2-halopyrazine in the presence of a palladium catalyst and a quaternary ammonium salt.
[0241] In another specific embodiment of step 2-2, the quaternary ammonium salt is selected from organic quaternary ammonium salts including tetrabutylammonium fluoride, tetrabutylammonium bromide, tetraethylammonium fluoride, tetraethylammonium bromide, tetramethylammonium fluoride, tetramethylammonium bromide, or tetramethylammonium chloride; preferably, tetrabutylammonium fluoride.
[0242] In another specific embodiment of step 2-2, the palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, palladium acetate, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium, palladium dichloride or bis(triphenylphosphine)palladium dichloride; preferably, 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or bis(triphenylphosphine)palladium dichloride; preferably, 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride.
[0243] In another specific embodiment of step 2-2, the molar ratio of 2-halopyrazine to compound B or its boronic acid hydrolysis product or a mixture thereof is 0.8-1.5:1; preferably, 1.2:1.
[0244] In another specific embodiment of step 2-2, the amount of base is 1 to 3.5 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof; preferably, 1.2 to 2.7 times; preferably, 1.2 times, 1.5 times, 1.8 times, 2.0 times, 2.1 times, 2.2 times, 2.4 times or 2.7 times.
[0245] In another specific embodiment of step 2-2, the amount of the palladium catalyst is 0.005 to 0.1 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof; preferably, 0.01 to 0.05 times; preferably, 0.01 times, 0.02 times, 0.03 times, 0.04 times, or 0.05 times the amount of compound B or its boronic acid hydrolysis product or a mixture thereof.
[0246] In another specific embodiment of step 2-2, the reaction is carried out in a solvent selected from DCM, DCE, ethyl acetate, methyl acetate, isopropyl acetate, n-hexane, n-heptane, petroleum ether, acetone, acetonitrile, toluene, methyl tert-butyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, isopropanol, water, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, DMF, DMA, DMSO, or a mixture thereof; preferably, the solvent is selected from tetrahydrofuran, 2-methyltetrahydrofuran, ethylene glycol monomethyl ether, isopropanol, water, toluene, DMF, DMSO, or a mixture thereof; preferably, the solvent is tetrahydrofuran, DMF, isopropanol, water, toluene, or a mixture thereof.
[0247] In another specific embodiment of step 2-2, the reaction is carried out at a temperature ranging from room temperature to solvent reflux, preferably 30-80° C., or more preferably 30±5° C., 50±5° C., 65±5° C. or 80±5° C.; preferably for a reaction time of at least 1 hour, preferably at least 3 hours.
[0248] Process 3 [ka]
[0249] In step 3, the VII type crystal of compound A is converted to the VII type crystal of compound A. In one embodiment, step 3 comprises dissolving the VII type crystal of compound A in acetone solution, concentrating at atmospheric pressure, then adding n-heptane in two portions, and then distilling at atmospheric pressure. In one embodiment, the temperature is 75±5° C. This crystal conversion produces a substantially pure VI type crystal of compound A.
[0250] The process of the present application is an improvement over the processes disclosed in the prior art. The preparation of Compound A is disclosed in International Publication No. WO 2018 / 133827 A1 (also referred to herein as the "'827 Publication").
[0251] A method for preparing compound A of the '827 publication is depicted below in Scheme 2.
[0252] Scheme 2 [ka]
[0253] There are many differences between the '827 method and the method of the present disclosure. At least some of the differences between the two methods are set forth in Table A below:
[0254] Table A: Differences between the '827 method and the method of the present disclosure [Table 19]
[0255] The differences between the disclosed method and the '827 method lead to significant improvements in the '827 method, including optimization of scale, safety, increased yield, improved purity, and overall process. The '827 method also suffers from a shortcoming in separation, namely, purification of the reaction products by column, a very expensive separation method that is not available on an industrial scale, in all steps. In contrast, the disclosed method uses centrifugation, filtration, and recrystallization for separation, making it suitable for larger scale production.
[0256] Substantially pure VI crystals of compound A The present disclosure provides a method for synthesizing Compound A Form VI crystals with high purity and high chiral purity that is safe, suitable for large-scale production, and can be used in compositions containing Compound A Form VI crystals. Meanwhile, Compound A Form VI crystals are produced by a commercial-scale method. The term "commercial-scale method" refers to a method of at least about 100 g of a single run. Meanwhile, the method of the present application produces Compound A Form VI crystals with limited impurities in improved yield (>90%).
[0257] The term "purity" as used herein refers to the content of Compound A VI crystals based on HPLC. Purity is based on the "organic" purity of the compound. Purity does not include water, solvents, metals, inorganic salts, etc. The purity of Compound A VI crystals is compared to the purity of a reference standard by comparing the area under the peak.
[0258] In one embodiment, the VI type crystal of Compound A has a purity of about 96% or more. In another embodiment, the VI type crystal of Compound A has a purity of about 98% or more. In yet another embodiment, the VI type crystal of Compound A has a purity of about 98.5% or more. In yet another embodiment, the VI type crystal of Compound A has a purity of about 99% or more. In yet another embodiment, the VI type crystal of Compound A has a purity of about 99.5% or more. In yet another embodiment, the VI type crystal of Compound A has a purity of 96.0%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 97.0%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97. and having a purity of 8%, 97.9%, 98.0%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8% or 99.9%.
[0259] The VI type crystal of compound A prepared in the present disclosure contains one chiral carbon atom and is in the R configuration. The chiral center of the VI type crystal of compound A is introduced from the starting material and is not involved in the subsequent process. Furthermore, no racemization is observed.
[0260] The term "chiral purity" as used herein refers to the chiral purity of Compound A VI crystals as measured by chiral HPLC. Chiral purity is based on the "organic" purity of the compound. Chiral purity is independent of water, solvents, metals, inorganic salts, etc. The chiral purity of Compound A VI crystals is compared to the chiral purity of a reference standard by comparing the areas under the peaks.
[0261] In one embodiment, the VI crystal of Compound A has a chiral purity of about 96% or more. In another embodiment, the VI crystal of Compound A has a chiral purity of about 98% or more. In yet another embodiment, the VI crystal of Compound A has a chiral purity of about 99% or more. In yet another embodiment, the VI crystal of Compound A has a chiral purity of about 99.4% or more. In another embodiment, the VI crystal of Compound A has a chiral purity of 96.0%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 97.0%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, having a chiral purity of 97.9%, 98.0%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8% or 99.9%.
[0262] In one embodiment, the present disclosure relates to a crystalline form VI of Compound A that contains less than about 0.8% total impurities.In another embodiment, the total impurities are less than about 0.5%.In yet another embodiment, the total impurities are less than about 0.3%.In yet another embodiment, the total impurities are less than about 0.2%.
[0263] In one embodiment, the present disclosure relates to Compound A VI crystals containing about 1% or less water, about 0.8% or less water, about 0.7% or less water, about 0.6% or less water, about 0.5% or less water, about 0.4% or less water, about 0.3% or less water, about 0.2% or less water, about 0.1% or less water, about 0.09% or less water, about 0.08% or less water, about 0.07% or less water, about 0.06% or less water, about 0.05% or less water. In another embodiment, the present disclosure relates to Compound A VI crystals containing about 0.11% or less water. In yet another embodiment, the present disclosure relates to Compound A VI crystals containing about 0.1% or less water. In yet another embodiment, the present disclosure relates to Compound A VI crystals containing about 0.09% or less water.
[0264] Pharmaceutical Compositions In another aspect, the present disclosure provides a pharmaceutical composition comprising: (i) a pharma- ceutical active ingredient: a crystalline form of Compound A free base or a pharma- ceutical acceptable salt thereof; (ii) a diluent; (iii) a disintegrant; (iv) a glidant; and (v) a lubricant.
[0265] In a specific embodiment of the above aspect, the active pharmaceutical ingredient is a crystalline form of the free base of Compound A; preferably, the crystalline form is selected from a crystalline form I of Compound A, a crystalline form II of Compound A, a crystalline form III of Compound A, a crystalline form IV of Compound A, a crystalline form V of Compound A, a crystalline form VI of Compound A, a crystalline form VII of Compound A, a crystalline form VIII of Compound A, a crystalline form IX of Compound A, a crystalline form X of Compound A, and a crystalline form XI of Compound A; preferably, the crystalline form is selected from a crystalline form I of Compound A, a crystalline form IV of Compound A, a crystalline form VI of Compound A, and a crystalline form XI of Compound A. In another specific embodiment, the pharma- ceutically active ingredient is a Form I crystal of the hydrochloride salt of Compound A, a Form I crystal of the benzenesulfonate salt of Compound A, a Form I crystal of the p-toluenesulfonate salt of Compound A, a Form II crystal of the p-toluenesulfonate salt of Compound A, a Form I crystal of the mesylate salt of Compound A, or a Form I crystal of the hydrobromide salt of Compound A; preferably, the Form I crystal is selected from a Form I crystal of the benzenesulfonate salt of Compound A, a Form I crystal of the p-toluenesulfonate salt of Compound A, a Form II crystal of the p-toluenesulfonate salt of Compound A, or a Form I crystal of the mesylate salt of Compound A.
[0266] In another aspect, the disclosure provides a pharmaceutical composition as described above, wherein the pharma- ceutical active ingredient is 1%-30% by weight, preferably 5%-20% by weight, preferably 8%-15% by weight, or more preferably about 10% by weight of the total weight of the pharmaceutical composition, based on the weight of the free base of the compound; preferably, the amount of the pharma- ceutical active ingredient in a unit dose is 1-100 mg, preferably 5-50 mg, preferably 8-40 mg, preferably about 10 mg, 20 mg, 30 mg, or 40 mg.
[0267] In another aspect, the disclosure provides a pharmaceutical composition as described above, wherein the diluent is 65% to 95% by weight, preferably 70% to 90% by weight, preferably about 80% by weight, 81% by weight, 82% by weight, 83% by weight, 84% by weight or 85% by weight of the total weight of the pharmaceutical composition; preferably, the amount of diluent in a unit dose is 65 to 380 mg, preferably 70 to 360 mg, preferably 80 to 350 mg, e.g., about 83 mg or 332 mg.
[0268] In another embodiment, the disclosure provides the pharmaceutical composition as described above, wherein the diluent is selected from lactose monohydrate, microcrystalline cellulose, anhydrous calcium hydrogen phosphate, mannitol and pregelatinized starch, and mixtures thereof; preferably, the microcrystalline cellulose is microcrystalline cellulose 102; and the lactose monohydrate is selected from lactose monohydrate Granulac 200, lactose monohydrate Tablettose 80 and lactose monohydrate FLOWLAC® 100; preferably, when both lactose monohydrate and microcrystalline cellulose are present, the weight ratio of lactose monohydrate to microcrystalline cellulose is 5:1 to 1:5, preferably 2:1 to 1:3, preferably about 1:2, e.g., 1:1.96.
[0269] In another aspect, the present disclosure provides the pharmaceutical composition as described above, wherein the disintegrant is 1 wt% to 5 wt%, preferably 2 wt% to 4 wt%, preferably about 3 wt% of the total weight of the pharmaceutical composition; preferably, the amount of the disintegrant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
[0270] In another embodiment, the present disclosure provides the aforementioned pharmaceutical composition, wherein the disintegrant is croscarmellose sodium.
[0271] In another aspect, the disclosure provides the aforementioned pharmaceutical composition, wherein the glidant is in an amount of 1 wt% to 5 wt%, preferably 2 wt% to 4 wt%, preferably about 3 wt% of the total weight of the pharmaceutical composition; preferably, the amount of (iv) glidant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
[0272] In another embodiment, the present disclosure provides the aforementioned pharmaceutical composition, wherein the glidant is colloidal silica.
[0273] In another aspect, the present disclosure provides the pharmaceutical composition as described above, wherein the lubricant is in an amount of 0.1 wt% to 5 wt%, preferably 0.5 wt% to 2 wt%, preferably about 1 wt% of the total weight of the pharmaceutical composition; preferably, the amount of lubricant in a unit dose is 0.1 to 20 mg, preferably 0.5 to 8 mg, preferably about 1 mg, 2 mg, 3 mg or 4 mg.
[0274] In another embodiment, the present disclosure provides a pharmaceutical composition as described above, wherein the lubricant is magnesium stearate or sodium stearyl fumarate.
[0275] In another aspect, the present disclosure relates to a pharmaceutical composition as described above, comprising the following components: (i) 1% by weight to 30% by weight of a VI type crystal of compound A; (ii) 70% to 90% by weight of lactose monohydrate and microcrystalline cellulose (1:2 by weight); (iii) 2% by weight to 4% by weight of croscarmellose sodium; (iv) 2% to 4% by weight of colloidal silica, and (v) 0.1% by weight to 5% by weight of magnesium stearate, The present invention provides a pharmaceutical composition comprising:
[0276] In an embodiment, the present disclosure relates to a pharmaceutical composition as described above, wherein the unit dose comprises the following ingredients: (i) about 10 mg of type VI crystal of Compound A; (ii) about 28 mg lactose monohydrate and about 55 mg microcrystalline cellulose; (iii) about 3 mg of croscarmellose sodium; (iv) about 3 mg of colloidal silica, and (v) about 1 mg of magnesium stearate; The present invention provides a pharmaceutical composition comprising:
[0277] In an embodiment, the present disclosure relates to a pharmaceutical composition as described above, wherein the unit dose comprises the following ingredients: (i) about 40 mg of type VI crystal of Compound A; (ii) about 112 mg lactose monohydrate and about 220 mg microcrystalline cellulose; (iii) about 12 mg of croscarmellose sodium; (iv) about 12 mg of colloidal silica, and (v) about 4 mg magnesium stearate; The present invention provides a pharmaceutical composition comprising:
[0278] In another aspect, the present disclosure provides a method for the preparation of a (i) a compound represented by formula (A), (ii) a diluent, (iii) a disintegrant, (iv) a glidant, and (v) lubricants, A pharmaceutical composition comprising: The diluent provides a pharmaceutical composition in an amount of 1% to 5% by weight, preferably 2% to 4% by weight, preferably about 3% by weight, of the total weight of the pharmaceutical composition.
[0279] In another embodiment, the present disclosure provides the aforementioned pharmaceutical composition, wherein the glidant is colloidal silica.
[0280] In another aspect, the present disclosure provides the aforementioned pharmaceutical composition, wherein the content of the glidant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
[0281] In another aspect, the disclosure provides the pharmaceutical composition as described above, wherein the diluent is 65% to 95% by weight, preferably 70% to 90% by weight, preferably about 80% by weight, 81% by weight, 82% by weight, 83% by weight, 84% by weight or 85% by weight of the total weight of the pharmaceutical composition; preferably, the amount of diluent in a unit dose is 65 to 380 mg, preferably 70 to 360 mg, preferably 80 to 350 mg, e.g., about 83 mg or 332 mg.
[0282] In another embodiment, the disclosure provides a pharmaceutical composition as described above, wherein the diluent is selected from lactose monohydrate, microcrystalline cellulose, anhydrous calcium hydrogen phosphate, mannitol and pregelatinized starch, and mixtures thereof; preferably, when both lactose monohydrate and microcrystalline cellulose are present, the weight ratio of lactose monohydrate to microcrystalline cellulose is 5:1 to 1:5, preferably 2:1 to 1:3, preferably about 1:2, for example 1:1.96.
[0283] In another aspect, the present disclosure provides the pharmaceutical composition as described above, wherein the disintegrant is present in an amount of 1 wt% to 5 wt%, preferably 2 wt% to 4 wt%, preferably about 3 wt% of the total weight of the pharmaceutical composition; preferably, the content of the disintegrant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
[0284] In another embodiment, the present disclosure provides the aforementioned pharmaceutical composition, wherein the disintegrant is croscarmellose sodium.
[0285] In another aspect, the present disclosure provides the pharmaceutical composition as described above, wherein the lubricant is in an amount of 0.1 wt% to 5 wt%, preferably 0.5 wt% to 2 wt%, preferably about 1 wt% of the total weight of the pharmaceutical composition; preferably, the amount of lubricant in a unit dose is 0.1 to 20 mg, preferably 0.5 to 8 mg, preferably about 1 mg, 2 mg, 3 mg or 4 mg.
[0286] In another embodiment, the present disclosure provides a pharmaceutical composition as described above, wherein the lubricant is magnesium stearate or sodium stearyl fumarate.
[0287] The present disclosure also provides a method for preparing a tablet, comprising: a) mixing a crystalline form of Compound A free base or a salt thereof, a diluent, a disintegrant and a glidant to form a mixture; and b) adding a lubricant to the mixture described in a).
[0288] The present disclosure provides a method for treating a Bcr-Abl-mediated disease or disorder in a subject, comprising administering to the subject an effective amount of a crystalline form of the free base of Compound A. In some embodiments, the subject is a human subject.
[0289] The compounds disclosed herein are particularly effective against diseases or disorders that depend on the activity of Bcr-Abl1. In particular, the compounds disclosed herein inhibit the ATP binding site of Bcr-Abl1 (including wild-type Bcr-Abl1 and / or its mutations, including T315I mutation).
[0290] Cancer cells utilize invapodia to degrade extracellular matrix during tumor invasion and metastasis. Abl kinase activity is required for Src-induced invapodia formation and regulates different stages of invadopodia assembly and function. Thus, the compounds disclosed herein, as inhibitors of Abl, have the potential to be used as therapeutics for the treatment of metastatic invasive cancer.
[0291] Inhibitors of c-Abl kinase can be used to treat brain cancers: including glioblastoma, the most common and most aggressive malignant primary brain tumor, where expression of c-Abl is detected immunohistochemically in a subset of patients. Thus, new c-Abl inhibitors with high brain exposure represent a promising therapeutic avenue for glioblastoma and other brain cancers.
[0292] The compounds disclosed herein are useful for the treatment of viruses.For example, viral infections can be mediated by Abl1 kinase activity, such as in the case of poxviruses and Ebola viruses.Imatinib and nilotinib have been shown to stop the release of Ebola virus particles from infected cells in vitro.Therefore, the compounds disclosed herein that inhibit c-Abl kinase can be expected to reduce the replication ability of pathogens.
[0293] Parkinson's disease is the second most common chronic neurodegenerative disorder, with the most common familial autosomal recessive form caused by mutations in the E3 ubiquitin ligase parkin. Recent studies have found activated c-ABL in the striatum of patients with sporadic Parkinson's disease. Concomitantly, parkin was tyrosine phosphorylated, causing a loss of its ubiquitin ligase and cytoprotective activity, as indicated by the accumulation of parkin substrates.
[0294] The compounds or compositions described herein are also useful for diseases, disorders or conditions mediated by Bcr-Abl kinase: respiratory diseases, allergies, rheumatoid arthritis, osteoarthritis, rheumatic disorders, psoriasis, ulcerative colitis, Crohn's disease, septic shock, proliferative disorders, atherosclerosis, allograft rejection after transplantation, diabetes, stroke, obesity or restenosis, leukemia, stromal tumors, thyroid cancer, systemic mastocytosis, eosinophilic syndromes, fibrosis, rheumatoid arthritis, polyarthritis, scleroderma, lupus erythematosus, graft versus host disease, neurofibromatosis. , pulmonary hypertension, Alzheimer's disease, seminoma, dysgerminoma, mast cell tumor, lung cancer, bronchial carcinoma, dysgerminoma, testicular intraepithelial neoplasia, melanoma, breast cancer, neuroblastoma, papillary / follicular parathyroid hyperplasia / adenoma, colon cancer, colorectal adenoma, ovarian cancer, prostate cancer, glioblastoma, brain tumor, malignant glioma, pancreatic cancer, malignant pleural tumor, hemangioblastoma, hemangioma, kidney cancer, liver cancer, adrenal gland cancer, bladder cancer, stomach cancer, rectal cancer, vaginal cancer, cervical cancer, endometrial cancer, multiple myeloma, head and neck tumors, neoplasia and other proliferative diseases or proliferative diseases, or combinations thereof. EXAMPLES
[0295] Common Method 1. X-ray Powder Diffraction (XRPD)
[0296] The solid samples obtained from the experiments were analyzed on a D8 Advance powder X-ray diffraction analyzer (Bruker) equipped with a LynxEye detector with a 2θ scan angle of 3° to 40° and a scan step length of 0.02°. The lamp voltage and lamp current when the samples were measured were 40 KV and 40 mA, respectively.
[0297] General method 2. Polarized light microscopy (PLM)
[0298] The model of the instrument used for PLM analysis was an ECLIPSE LV100POL polarizing microscope (Nikon, Japan).
[0299] General method 3. Nuclear magnetic resonance hydrogen spectroscopy analysis ( 1 H NMR)
[0300] The chemical structure of the solid sample is 1 Confirmed by 1 H NMR. 1 H NMR analyses were performed using a Bruker Advance 300 equipped with a B-ACS 120 autosampling system.
[0301] Common Method 4. Differential Scanning Calorimetry (DSC)
[0302] The differential scanning calorimetry analysis was performed using a DSC Q200 or Discovery DSC 250 (TA, USA). The samples were accurately weighed and placed in a perforated sample pot for DSC, and the exact mass of the sample was recorded. The samples were heated to the final temperature (e.g., 300°C or 350°C) at a ramp rate of 10°C / min.
[0303] Common Method 5. Thermogravimetric Analysis (TGA)
[0304] The thermogravimetric analyzer model was TGA Q500 or Discovery TGA 55 (TA, USA). Samples were placed in equilibrated open aluminum sample pots and automatically weighed in the TGA furnace. Samples were heated to the final temperature (e.g., 300°C or 350°C) at a ramp rate of 10°C / min.
[0305] General Method 6. Dynamic Water Sorption-Desorption Analysis (DVS)
[0306] The instrument model of the apparatus used for dynamic moisture sorption / desorption analysis was IGA Sorp (Hidentity Isochema). Samples were measured in a gradient mode with a moisture content ranging from 0% to 90% and a humidity increase of 10% for each gradient.
[0307] Example 1 Preparation of Compound A Using the method of Example 7 of WO 2018 / 133827 A1, compound A was prepared as follows: Preparation of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (compound 17) [ka] Step 1: Synthesis of 6-chloro-5-bromo-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (compound 3) 6-Chloro-5-bromonicotinic acid (1.17 g, 4.97 mmol) and 4-(chlorodifluoromethoxy)aniline (0.8 g, 4.15 mmol) were added to the reaction flask and dissolved in 20 mL of anhydrous DMF. 2-(7-aza-1H-benzotriazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HATU, 2.1 g, 5.39 mmol) and N,N-diisopropylethylamine (DIPEA, 534 mg, 4.15 mmol) were added and the reaction was stirred for 18 h under nitrogen protection. The reaction mixture was diluted with a large amount of water and extracted with ethyl acetate 3-4 times. The organic phases were combined, washed with saturated brine, concentrated, purified by column chromatography, and dried in vacuum to give 1.18 g of product (yield: 69.5%). Step 2: Synthesis of (R)-6-(3-fluoropyrrolidin-1-yl)-5-bromo-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (Compound 15) Compound 3 (0.90 g, 2.19 mmol) and (R)-3-fluoropyrrolidine hydrochloride (330 mg, 2.63 mmol) were added to a reaction flask. 15 mL of isopropyl alcohol and DIPEA (621 mg, 4.82 mmol) were added. The mixture was heated to 140° C. and reacted with stirring for 2 hours. After cooling to room temperature, the reaction mixture was concentrated to remove the solvent. The residue was purified by silica gel column chromatography to give 841 mg of product (yield: 83%). Step 3: Synthesis of (R)-6-(3-fluoropyrrolidin-1-yl)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (compound 16) A reaction flask was charged with compound 15 (628 mg, 1.35 mmol), bis(pinacolato)diboron (1.03 g, 4.06 mmol), palladium acetate (10 mg, 0.041 mmol), Xphos (50 mg, 0.101 mmol) and potassium phosphate (861 mg, 4.06 mmol). The mixture was dissolved by adding 20 mL of anhydrous dioxane. The solution was heated to 60° C. in a microwave and reacted for 4 h. TLC showed that the starting material was not completely consumed. Additional bis(pinacolato)diboron (1.03 g, 4.06 mmol) was added and then the mixture was stirred at 60° C. overnight. TLC showed that the reaction was complete. The reaction mixture was concentrated and purified by silica gel column chromatography to give 514.3 mg of product (yield: 75%). Step 4: Synthesis of (R)-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrolidin-1-yl)-5-(pyrazin-2-yl)nicotinamide (compound 17).
[0308] To a reaction flask was added compound 16 (200 mg, 0.372 mmol), 2-bromopyrazine (50 mg, 0.27 mmol), Pd(dppf)Cl2 (10 mg, 0.01 mmol) and sodium carbonate (60 mg, 0.558 mmol). 5 mL of glycol dimethyl ether and 0.9 mL of water were added, and the mixture was bubbled with nitrogen gas for 10 min. The mixture was heated to 100° C. in a microwave and reacted for half an hour. TLC showed that the reaction was complete. The reaction mixture was concentrated and purified by silica gel column chromatography to give 35 mg of product (yield: 20.3%). LC-MS(APCI): m / z = 464.5 (M+1)+. 1H NMR (400 MHz, CDCl3) δ 8.78 (d, J = 2.0 Hz, 1H), 8.73 (s, 1H), 8.64 (s, 1H), 8.54 (d, J = 2.1 Hz, 1H), 8.11 (d, J = 2.0 Hz, 1H), 7.95 (s, 1H), 7.67 (d, J = 8.9 Hz, 2H), 7.23 (d, J = 8.6 Hz, 2H), 5.28 (s, 1H), 5.14 (s, 1H), 3.70 - 3.57 (m, 1H), 3.52 (d, J = 10.8 Hz, 1H), 3.42 (t, J = 11.6 Hz, 1H), 3.30 (t, J = 9.5 Hz, 1H), 2.26 - 2.17 (m, 1H), 2.02 (dd, J = 9.5, 3.8 Hz, 1H).
[0309] Compound A was recrystallized from absolute ethanol to obtain type I crystals, which were named type I crystals.
[0310] Example 2 Large-scale production of Form VI crystals of Compound A Crystalline Form VI of Compound A was prepared in three batches on a kilogram scale using the process of Scheme 1.
[0311] Example 2.1 Preparation of the starting material 5-bromo-6-chloro-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (compound D) [ka]
[0312] Dichloromethane (4 vol), 5-bromo-6-chloronicotinic acid (1.0 eq) and DMF (0.05 eq) were added to the reactor and the mixture was stirred. The temperature was controlled not to exceed 5° C. Dichlorosulfoxide (2.0 eq) was slowly added dropwise. After the addition was complete, the mixture was heated to 40° C. at reflux. The mixture was stirred for at least 20 hours. A sample was then taken to detect 5-bromo-6-chloronicotinic acid by HPLC until it was less than 2.0%. The mixture was cooled to room temperature and concentrated under reduced pressure. Additional ethyl acetate was added and the mixture was concentrated. This operation was repeated. Ethyl acetate was added (up to 5 vol) to dilute and dissolve for later use (solution of acyl chloride intermediate in ethyl acetate).
[0313] Water (4 vol) and sodium carbonate (2.0 equiv.) were added sequentially to the reactor under nitrogen. The mixture was stirred until clear. Ethyl acetate (2 vol.) and 4-(chlorodifluoromethoxy)aniline (0.95 equiv.-1.0 equiv.) were added. A solution of acyl chloride intermediate in ethyl acetate was slowly added dropwise while controlling the temperature below 5°C. The mixture was stirred at room temperature for 1 hour, a sample was taken, and monitored by HPLC. The mixture was concentrated under reduced pressure at 45°C to remove ethyl acetate and filtered by suction. The filter cake was washed with water. The filter cake was collected and dried in a vacuum oven at 45°C. The purity of the starting material 5-bromo-6-chloro-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide was detected by an appropriate HPLC method.
[0314] According to the above synthesis method, three batches of 5-bromo-6-chloro-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (Compound D) were prepared on a pilot kilogram scale and the results are listed in Table 2.1.
[0315] [Table 20]
[0316] Example 2.2 Preparation of VI-type crystals of Compound A
[0317] Step 1: Preparation of (R)-5-bromo-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrol-1-yl)nicotinamide (Compound C) [ka]
[0318] DMSO (3 vol) was added to reactor A under nitrogen, 5-bromo-6-chloro-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide (1.0 eq), 3-(R)-fluoropyrrolidine hydrochloride (1.0 eq) and anhydrous sodium carbonate (2.2 eq) were added under stirring. The mixture was heated to 70±10°C and reacted at this temperature with stirring for at least 22 hours. Samples were taken and detected by HPLC until the reaction was complete (standard: 5-bromo-6-chloro-N-(4-(chlorodifluoromethoxy)phenyl)nicotinamide ≤ 2.0%). The mixture was cooled to 20-30°C for later use. Demineralized water (18 vol) was added to reactor B under nitrogen. The reaction solution in reactor A was added dropwise to reactor B while controlling the temperature at 20-30°C. After the addition was complete, the mixture was stirred at the controlled temperature for at least 15 minutes. The mixture was centrifuged under nitrogen in a centrifuge and the precipitate was washed with demineralized water. The precipitate was collected.
[0319] The precipitate was dried under vacuum at 55±5°C for at least 10 hours. A slight stream of nitrogen gas was passed through the precipitate during drying and a sample was taken for KF detection (standard: KF≦4.0%). The baking was stopped and the precipitate was cooled to below 30°C. A sample was taken, detected by HPLC and the precipitate was collected. The product was placed in a double LDPE bag and the bag was tied tightly. Approximately 10% of the product weight of desiccant was placed between the second and third layer of the LDPE bag. The mixture was weighed, labeled as intermediate and temporarily stored at room temperature.
[0320] According to the above synthesis method, three batches of (R)-5-bromo-N-(4-(chlorodifluoromethoxy)phenyl)-6-(3-fluoropyrrol-1-yl)nicotinamide were prepared in pilot kilogram scale and the results are listed in Table 2.2-1.
[0321] [Table 21]
[0322] Step 2: Preparation of Type VII Crystals of Compound A
[0323] Process 2-1: [ka]
[0324] Step 2-2: [ka]
[0325] Step 2-1: Preparation of (R)-(5-((4-(chlorodifluoromethoxy)phenyl)carbamoyl)-2-(3-fluoropyrrolidin-1-yl)pyridin-3-yl)boronic acid (compound B) or its boronic acid hydrolysis product or mixture thereof
[0326] The applicant has conducted in-depth research into the reaction for obtaining compound B and carried out stepwise optimization of various conditions in the reaction, as detailed below. [ka]
[0327] In the table below the following abbreviations have been used: [ka]
[0328] 1) Optimize the amount of B2Pin2 [Table 22]
[0329] 2) Optimization of solvent type [Table 23]
[0330] 3) Optimization of the amount of solvent [Table 24]
[0331] 4) Optimization of base groups [Table 25]
[0332] 5) Optimization of catalysts and ligands [Table 26]
[0333] 6) Optimization of the amount of base and B2Pin2 [Table 27]
[0334] After the above optimization, three optimized batch preparations for scale-up are provided below.
[0335] Under nitrogen, a reaction vessel was charged with DMSO (10 vol.), compound C (1.0 equiv.), bis(pinacolato)diboron (3.0 equiv.), potassium acetate (2.5 equiv.), 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (0.05 equiv.) and purified water. # ((3.7%-KF)*m / 2, kg)) was added sequentially under stirring. The mixture was heated to 80±10°C and stirred at controlled temperature for at least 2 h. Additional purified water was added under nitrogen. # ((3.7%-KF)*m / 2, kg)) was added and the mixture was reacted for at least 2 hours while maintaining the temperature. Samples were taken and the reaction progress was monitored by HPLC (Standard: Compound C ≦ 2.0%) (#: m is the mass of Compound C, and KF is the KF of Compound C). If the reaction was not complete, the mixture was cooled to 20-30 °C and additional 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (0.01 equiv.) was added under nitrogen. The mixture was heated to 80 ± 10 °C and stirred for at least 2 h while maintaining the temperature. A sample was taken and sent to HPLC to monitor the reaction until completion. The mixture was cooled to room temperature and filtered by suction. The filtrate was collected and concentrated under reduced pressure to 1.0-1.5 volumes and n-heptane was added. The mixture was stirred and the precipitate was collected.
[0336] The precipitate was dried under vacuum at 40±5° C. for at least 12 hours, then the baking was stopped. The precipitate was cooled to below 30° C. and then maintained at this temperature for at least 1 hour. The precipitate was then collected.
[0337] Step 2-2: Preparation of Compound A and its Type VII Crystal
[0338] The applicant has conducted in-depth research into the reaction for obtaining compound A and carried out stepwise optimization of various conditions in the reaction, as detailed below: [ka]
[0339] In the tables below, the following abbreviations have been used: [ka]
[0340] 1) Optimization of halopyrazines [Table 28]
[0341] 2) Optimization of base types [Table 29-1] [Table 29-2]
[0342] 3) Optimization of the amount of catalyst using a 1M solution of Bu4NF in THF as a base [Table 30]
[0343] 4) Optimization of the type and amount of catalyst using K3PO4 as a base [Table 31]
[0344] 5) Optimization of the solvent using a 1M solution of Bu4NF in THF as a base [Table 32]
[0345] 6) Optimization of temperature using a 1M solution of Bu4NF in THF as base [Table 33]
[0346] 7) Optimization of the amount of solvent using K3PO4 as a base [Table 34]
[0347] 8) Temperature optimization using K3PO4 as base [Table 35]
[0348] After the above optimization, three batches of optimized preparation for scale-up were provided below:
[0349] Tetrahydrofuran (5 vol.) was added to the reactor under nitrogen. Compound B (1.0 eq.), 2-iodopyrazine (1.2 eq.), tetrabutylammonium fluoride (1M solution in tetrahydrofuran) (2.7 eq.), and 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (0.01 eq.) were added sequentially under stirring. The mixture was heated to 65±5°C and reacted for at least 3 hours while maintaining this temperature. A sample was taken and sent to HPLC to monitor the reaction until completion. The mixture was cooled to room temperature and filtered by suction. The filtrate was collected, washed with water, concentrated, and then recrystallized.
[0350] Recrystallization (I): To the reactor under nitrogen was added absolute ethanol (7 vol.) and p-toluenesulfonic acid monohydrate (1.5 eq.). The mixture was heated to 75±5°C and stirred while maintaining this temperature for at least 1 hour. The mixture was cooled to 20-30°C and stirred while maintaining this temperature for at least 3 hours. The mixture was centrifuged and rinsed with absolute ethanol. The precipitate was collected. To the reactor under nitrogen were added acetone (6 vol.), demineralized water (6 vol.), filter cake (1.0 eq.) and anhydrous sodium carbonate (1.5 eq.) in sequence and the mixture was stirred at 20-30°C for at least 1 hour. The external temperature was controlled at 45±5°C. The mixture was concentrated under reduced pressure to 6-8 volumes. The mixture was cooled to 20-30°C, centrifuged and rinsed with demineralized water. The precipitate was collected.
[0351] Slurrying: Demineralized water (10 volumes) was added under nitrogen and the precipitated material was added with stirring. The mixture was stirred for at least 1 hour while maintaining the temperature at 20-30°C. The mixture was centrifuged, rinsed with demineralized water and the precipitate was collected.
[0352] Recrystallization (II): Anhydrous ethanol (10 vol.) was added to the reactor under nitrogen. The filter cake and p-toluenesulfonic acid monohydrate (1.5 equiv.) were added with stirring. The mixture was heated to 75±5°C and stirred for at least 1 h while maintaining this temperature. The mixture was cooled to 20-30°C and stirred for at least 3 h while maintaining this temperature. The mixture was centrifuged, rinsed with anhydrous ethanol and the precipitate was collected. Acetone (6 vol.), demineralized water (6 vol.), filter cake (1.0 equiv.) and anhydrous sodium carbonate (1.5 equiv.) were added sequentially to the reactor under nitrogen and stirred at 20-30°C for at least 1 h. The external temperature was controlled at 45±5°C. The mixture was concentrated to 6-8 volumes under reduced pressure. The mixture was cooled to 20-30°C, centrifuged, rinsed with demineralized water and the precipitate was collected. A sample was taken for HPLC detection. If the criteria were not met, the operations of "slurrying recrystallization (I)" and "recrystallization (II)" were repeated until the criteria were met by HPLC detection. If the criteria were met, the operation of "slurrying recrystallization (I)" was performed, the precipitate was collected, and HPLC detection was performed until the criteria were met (criteria: purity of compound A VII type crystals ≧99.2%, impurity RRT0.37<0.10%).
[0353] The precipitate was dried under vacuum at 55±5°C for at least 12 hours and then the baking was stopped. The precipitate was cooled to below 30°C and held at this temperature for at least 1 hour. A sample was taken for visual inspection, identification, and HPLC to collect the precipitate. The product was placed in a 3-ply LDPE bag and the bag was tied tightly. A desiccant was placed between the second and third plies of the LDPE bag. The mixture was weighed, labeled as intermediate, and then temporarily stored at room temperature.
[0354] According to the above synthesis method, three batches of the VII type crystal of Compound A were prepared on a pilot kilogram scale, and the results are shown in Table 2.2-2:
[0355] [Table 36]
[0356] Step 3: Preparation of VI-type crystals of Compound A [ka]
[0357] Under nitrogen, a solution of Compound A Form VII crystals in acetone (1.0 equivalent dissolved in 15 volumes of acetone) that had been passed through a microporous cartridge was added to the reactor. The temperature was controlled at 50-80°C, and the mixture was evaporated to 7-9 volumes at atmospheric pressure. n-Heptane (7.5 volumes) that had been passed through a microporous cartridge was added, and the mixture was evaporated to 7-9 volumes at atmospheric pressure. n-Heptane (7.5 volumes) that had been passed through a microporous cartridge was added, and the mixture was evaporated to 7-9 volumes at atmospheric pressure. The internal temperature was increased to 75±5°C. The mixture was cooled to 20-30°C and stirred for at least 3 hours while maintaining this temperature. The mixture was centrifuged and washed with n-heptane that had been passed through a microporous cartridge. The precipitate was collected and dried under vacuum at 55±5°C for at least 12 hours. A small stream of nitrogen gas was introduced during the drying process. The precipitate was cooled below 30°C for at least 1 hour and a sample was taken for KF detection (standard: KF≦0.5%). A sample was taken for solvent residue detection (standard: acetone≦5000ppm, n-heptane≦5000ppm, tetrahydrofuran≦720ppm). A sample was submitted for HPLC analysis (standard: Compound A Form VI crystals have a purity of ≧99.2%). It was placed in a double-layered low density polyethylene bag. The bag was tied tightly and weighed. The outer aluminum foil bag was heat sealed and placed in a fiber drum. The product was stored in an airtight container at room temperature.
[0358] According to the above synthesis method, three batches of VI type crystals of compound A were prepared on a pilot kilogram scale, and the results are shown in Table 2.2-3: [Table 37]
[0359] Example 3 Preparation of various crystal forms of Compound A In the screening of various crystal forms of the free base of Compound A, Compound A was used as the starting material, and screening of various crystal forms of the free base of Compound A was carried out using several methods, such as cooling crystallization, evaporation crystallization, suspension crystallization conversion, dissolution-precipitation crystallization, heat treatment, and grinding crystallization. A total of 11 forms were found: one anhydrous crystal (Compound A VI crystal), two hydrate crystals (Compound A III crystal and Compound A VII crystal), and eight solvate crystals (Compound A I crystal, Compound A II crystal, Compound A IV crystal, Compound A V crystal, Compound A VIII crystal, Compound A IX crystal, Compound A X crystal, and Compound A XI crystal).
[0360] Example 3.1 Screening of 13x13 (1:1) binary solvents in 96-well plates
[0361] A certain amount of compound A type I crystals was added to 13 vials, and 3 mL of corresponding solvent (methanol, ethanol, isopropanol, isobutanol, 2-butanone, tetrahydrofuran, acetonitrile, methyl tert-butyl ether, acetone, water, toluene, ethyl acetate, isopropyl acetate, respectively) was gradually added, where compound A type I crystals formed suspensions in methanol, ethanol, isopropanol, isobutanol, toluene, methyl tert-butyl ether and water, and formed solutions in other solvents. 2 mL of suspension / solution was filtered, and the obtained filtrate was used for screening of binary solvents in 96-well plate. The above corresponding filtrates were distributed in 96-well plate in duplicate, with a volume of 100 μL for each filtrate. The 96-well plate was sealed with sealing film and evaporated to dryness in a fume hood at room temperature. The information of 13 kinds of solvents in 96-well plate is shown in Table 3.1.
[0362] Table 3.1: Information on 13x13 solvents in a 96 well plate [Table 38]
[0363] PLM and XRPD studies were performed on the solids precipitated in 96-well plates, and two new crystal forms, named Form II and Form III, were obtained, where Form II was obtained in acetonitrile / methyl tert-butyl ether; and Form III was obtained in acetone / water.
[0364] Example 3.2 Study of suspended crystal transformation in 13 single solvents
[0365] The suspensions of the I-type crystals of Compound A in methanol, ethanol, isopropanol, isobutanol, toluene, methyl tert-butyl ether and water left over from Example 3.1 were slurried and stirred at room temperature for 3 days. Solids were obtained in methanol, ethanol, isopropanol, isobutanol, water, toluene and methyl tert-butyl ether and were subjected to PLM and XRPD testing. The results showed that in addition to the I-type and III-type crystals, four new types of crystals were obtained in methanol, isobutanol, methyl tert-butyl ether and toluene. Specifically, the I-type crystals were obtained in suspension in ethanol, the III-type crystals in suspension in water; the IV-type crystals were obtained in suspension in methanol, which was a solvate of methanol; the V-type crystals were obtained in suspension in isobutanol, which was a solvate of isobutanol; the VI-type crystals were obtained in suspension in methyl tert-butyl ether, which was anhydrous; and the VII-type crystals were obtained in suspension in toluene, which was a hydrate.
[0366] Example 3.3 Evaporative crystallization study of 13 single solvents
[0367] The remaining 13 single filtrates for spreading the 96-well plate of Example 3.1 were dried in a fume hood. No solids were obtained in water, isopropanol, and isobutanol, but solids were found in all other solvents. The solids were examined by PLM and XRPD. As a result, in addition to the II, III, IV, and VII crystals, a new crystal type named VIII was obtained. Specifically, the II crystal type was obtained as an acetonitrile solvate by evaporation in a single solvent of acetonitrile; the III crystal type was obtained as a hydrate by evaporation in a single solvent of acetone; the IV crystal type was obtained as a methanol solvate by evaporation in a single solvent of methanol; the VII crystal type was obtained as a hydrate by evaporation in toluene; and the new crystal type named VIII was obtained as an ethanol solvate by evaporation in ethanol.
[0368] Example 3.4 Dissolution-precipitation crystallization studies
[0369] A specific amount of compound A was added to the corresponding solvent, and a specific amount of anti-solvent was added after compound A was dissolved. The test conditions and results are shown in Table 3.4.
[0370] [Table 39]
[0371] Form I crystals were used as starting material. Addition of antisolvent to acetonitrile / water, acetone / water, and ethyl acetate / n-heptane produced solids. Addition of antisolvent to tetrahydrofuran / water and tetrahydrofuran / n-heptane produced oils that became solids after 1 hour of stirring. Tetrahydrofuran / isopropanol and acetone / n-heptane produced solids after 15 minutes of stirring. Tetrahydrofuran / methyl tert-butyl ether and ethyl acetate / methyl tert-butyl ether produced solids after 3 hours of stirring. The other solutions became clear after stirring overnight. The resulting solids were examined by PLM and XRPD. XRPD results showed that in addition to type III crystals (hydrate) and type VI crystals (anhydrous type crystals), a new type crystal named type IX crystal was obtained as a solvate of isopropanol, ethanol and tetrahydrofuran in tetrahydrofuran / isopropanol, and another new type crystal named type X crystal was obtained as a solvate of tetrahydrofuran in tetrahydrofuran / water.
[0372] Example 3.5 Cooling Crystallization Studies
[0373] About 30 mg of the I-type crystals of Compound A were added to different solvents and heated until dissolved. The resulting solutions were then cooled slowly to room temperature. The test conditions and results are listed in Table 3.5. The solid crystals obtained were subjected to PLM and XRPD tests.
[0374] [Table 40]
[0375] According to the XRPD results, in addition to the IV type crystal, a new type crystal named XI type crystal was obtained as an acetonitrile solvate in acetonitrile.
[0376] Example 4 Characterization of various crystalline forms of the free base of Compound A The various crystal forms obtained in Example 3 were characterized.
[0377] Example 4.1 Characterization of Form I Crystals of Compound A
[0378] Form I crystals of the compound were prepared according to the method of Example 1, and were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0379] XRPD analysis
[0380] Figure 1 shows the XRPD data for crystalline Form I of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ° (°2θ) ± 0.2°2θ is shown in Table 4.1.
[0381] [Table 41]
[0382] PLM analysis
[0383] The collected Compound A Form I crystals were subjected to PLM analysis by General Method 2. The sample was observed to be irregular sheet-like particles with particle sizes less than 50 μm.
[0384] 1 H NMR analysis
[0385] Compound A type I crystal 1 The H NMR data is as follows: 1H NMR (300 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.4 Hz, 1H), 8.84 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.25 (d, J = 2.3 Hz, 1H), 7.93 - 7.79 (m, 2H), 7.35 (d, J = 9.0 Hz, 2H), 5.30 (d, J = 53.4 Hz, 1H), 3.63 - 3.45 (m, 1H), 3.41 - 3.34 (m, 2H), 3.27 - 3.18 (m, 1H), 2.20 - 1.87 (m, 2H).
[0386] DSC and TGA thermal analysis
[0387] The collected compound A type I crystals were subjected to DSC analysis by general method 4. DSC analysis showed a melting endothermic peak at 172.95°C with an onset temperature of 170.67°C. Compound A type I crystals were heated to 150°C by DSC, and then the solvent was removed. As shown in Figure 3, the type I crystals were transformed into type VI crystals.
[0388] The collected Form I crystals of Compound A were subjected to TGA analysis by General Method 5. TGA showed that it had about 5.1% weight loss before 200° C., mainly due to ethanol.
[0389] 1 H NMR, DSC and TGA analyses indicated that Form I crystals of Compound A were a solvate of ethanol.
[0390] DVS analysis
[0391] Figure 2 shows the DVS curve of the type I crystal of Compound A obtained by General Method 6. DVS analysis showed that the sample was slightly hygroscopic, with the water absorption rate being about 0.2% under 0-60% RH conditions, about 0.7% under 0-80% RH conditions, and about 1.3% under 0-90% RH conditions.
[0392] Example 4.2 Characterization of Crystalline Form II of Compound A
[0393] Form II crystals of Compound A were obtained by evaporation in acetonitrile single solvent according to the method of Example 3.3, and were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0394] XRPD analysis
[0395] Figure 4 shows the XRPD data for crystalline Form II of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ° (°2θ) ± 0.2°2θ is provided in Table 4.2.
[0396] [Table 42]
[0397] PLM analysis
[0398] The collected Form II crystals of Compound A were subjected to PLM analysis by General Method 2. The sample was observed to be in irregular chunks.
[0399] 1 H NMR analysis
[0400] Compound A type II crystal 1 The H NMR data is as follows: 1H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 3.51 (ddd, J = 39.8, 13.6, 3.4 Hz, 1H), 3.35 (s, 2H), 3.21 (t, J = 9.6 Hz, 1H), 2.18 - 1.91 (m, 2H).
[0401] DSC and TGA thermal analysis
[0402] The collected Form II crystals of Compound A were subjected to DSC analysis by general method 4. DSC analysis showed a melting endotherm peak at 115.17°C with an onset temperature of 109.08°C.
[0403] The collected Form II crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed a weight loss of about 1.9% before 200°C.
[0404] 1 H NMR, DSC and TGA analyses showed that crystalline Form II of Compound A was a solvate of acetonitrile.
[0405] Example 4.3 Characterization of Form III Crystals of Compound A
[0406] Form III crystals of Compound A were obtained by suspension crystal conversion in a single aqueous solvent according to the method of Example 3.2, and were characterized by XRPD, PLM, 1H NMR, DSC and TGA. The specific results are as follows:
[0407] XRPD analysis
[0408] Figure 5 shows the XRPD data for crystalline Form III of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ° (°2θ) ±0.2°2θ is provided in Table 4.3.
[0409] [Table 43]
[0410] PLM analysis
[0411] The collected Form III crystals of Compound A were subjected to PLM analysis by general method 2. The sample was observed to be in irregular chunks.
[0412] 1 H NMR analysis
[0413] Compound A type III crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.90 - 7.84 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.8 Hz, 1H), 3.56 (dd, J = 13.4, 3.3 Hz, 1H), 3.46 (dd, J = 13.2, 3.2 Hz, 2H), 3.21 (t, J = 9.5 Hz, 1H), 2.13 - 1.98 (m, 2H).
[0414] DSC and TGA thermal analysis
[0415] The collected Form III crystals of Compound A were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 172.83°C with an onset temperature of 171.83°C.
[0416] The collected Form III crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed that it had a weight loss of about 3.5% before 200°C.
[0417] 1 H NMR, DSC and TGA analyses showed that crystalline Form III of Compound A was a hydrate.
[0418] Example 4.4 Characterization of Form IV Crystals of Compound A
[0419] According to the method of Example 3.5, the IV form of Compound A was obtained by cooling crystallization in methanol solution and characterized by XRPD, PLM, 1H NMR, DSC and TGA. The specific results are as follows:
[0420] XRPD analysis
[0421] Figure 6 shows the XRPD data for crystalline Form IV of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ° (°2θ) ±0.2°2θ is provided in Table 4.4.
[0422] [Table 44]
[0423] PLM analysis
[0424] The collected Form IV crystals of Compound A were subjected to PLM analysis by General Method 2. The sample was observed to be microcrystalline.
[0425] 1 H NMR analysis
[0426] Compound A type IV crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.92 - 7.82 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.1 Hz, 1H), 3.59 - 3.44 (m, 1H), 3.36 (d, J = 6.5 Hz, 2H), 3.21 (t, J = 9.4 Hz, 1H), 2.15 - 1.95 (m, 2H).
[0427] DSC and TGA thermal analysis
[0428] The collected Form IV crystals of Compound A were subjected to DSC analysis by general method 4. DSC analysis showed a melting endotherm peak at 175.84° C. with an onset temperature of 174.03° C. There was also a higher endotherm peak with a peak temperature of 250.71° C. and an onset temperature of 250.64° C.
[0429] The collected Form IV crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed that it had a weight loss of about 3.7% before 200°C.
[0430] 1 H NMR, DSC and TGA analyses showed that Form IV crystal of Compound A was a solvate of methanol.
[0431] Example 4.5 Characterization of Form V Crystals of Compound A
[0432] Form V crystals of compound A were obtained by suspension crystal conversion in isobutanol single solution according to the method of Example 3.2, and characterized by XRPD, PLM, 1H NMR, DSC and TGA. The specific results are as follows:
[0433] XRPD analysis
[0434] Figure 7 shows the XRPD data for crystalline Form V of Compound A obtained according to General Method 1. A list of the XRPD peaks at diffraction angles 2θ° (°2θ) ± 0.2°2θ and their relative intensities is provided in Table 4.5.
[0435] [Table 45]
[0436] PLM analysis
[0437] The collected Compound A Form V crystals were subjected to PLM analysis by general method 2. The sample was observed to be microcrystalline.
[0438] 1 H NMR analysis
[0439] Compound A V-type crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.91 - 7.83 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.36 (d, J = 53.6 Hz, 1H), 3.59 - 3.54 (m, 1H), 3.50 - 3.42 (m, 2H), 3.27 - 3.16 (m, 1H), 2.14 - 1.96 (m, 2H).
[0440] DSC and TGA thermal analysis
[0441] The collected Compound A Form V crystals were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 173.42°C with an onset temperature of 171.38°C.
[0442] The collected Compound A Form V crystals were subjected to TGA analysis by General Method 5. The TGA analysis showed that it had a weight loss of about 6.5% before 200°C.
[0443] 1 H NMR, DSC and TGA analyses showed that Form V crystals of Compound A were a solvate of isobutanol.
[0444] Example 4.6 Characterization of Form VI Crystals of Compound A
[0445] According to the industrial method of Example 2, the VI type crystal of Compound A was obtained and characterized by XRPD, PLM, NMR, MS, UV, DSC, TGA, DVS and IR. The specific results are as follows:
[0446] XRPD analysis
[0447] Figure 8 shows the XRPD data for crystalline Form VI of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is shown in Table 4.6-1.
[0448] [Table 46]
[0449] PLM analysis
[0450] The collected Form VI crystals of Compound A were subjected to PLM analysis by General Method 2. The sample was observed to be microcrystalline.
[0451] NMR analysis
[0452] Instruments and equipment: Bruker AVANCE III 400 MHz NMR instrument, solvent: DMSO-d6.
[0453] Sample analysis: 52.15 mg of Compound A VI crystals was accurately weighed, and 0.6 mL of DMSO-d6 was added. After complete dissolution, the solution was transferred to an NMR tube. 1 H-NMR, 13 C-NMR, DEPT, 19 F-NMR, HSQC, HMBC, COSY, NOESY and HF NOESY were examined.
[0454] Structural fragment of compound A: [ka]
[0455] Critical HMBC and COSY related structures of compound A: [ka]
[0456] Figure 9 shows the nuclear magnetic resonance hydrogen spectrum of the VI crystal of Compound A. Table 4.6-2 shows the test results of the nuclear magnetic resonance hydrogen spectrum of the VI crystal of Compound A. The results show that there are 17 hydrogen signals in the hydrogen spectrum, including 7 methylene hydrogens, 9 methenyl hydrogens, and 1 active hydrogen. Chemical shift δ H The hydrogen signal at 10.28 (s, 1H) had no HSQC correlation and was assigned to NH-8 by chemical shift. H 7.89 (m, 2H) and δ H The hydrogen signals at chemical shifts of 7.35 (d, J = 9.2Hz, 2H) are typical characteristic signals of 1,4-disubstituted benzene rings and were assigned to H-3, 5, H-2, and 6 by HMBC (Table 3.6-5). H5.37, 5.24(d, J=52Hz, 1H), δH 3.53(ddd, J=40, 13.6, 3.2Hz, 1H), δ H 3.35 (overlapping, 1H), δ H 3.39-3.19 (overlapping, 2H), and δ H The hydrogen signals at 2.18-1.91 (m, 2H) were assigned to H-20, H-19a, H-19b, H-22, and H-21, respectively, based on the chemical shifts, coupling constants, and COSY (Table 3.6-6). The remaining hydrogen signals are consistent with the structure of compound A.
[0457] [Table 47]
[0458] 13 C-NMR FIG. 10 shows the nuclear magnetic resonance carbon spectrum of the VI type crystal of Compound A. FIG. 11 shows the DEPT NMR spectrum of the VI type crystal of Compound A, and Table 4.6-3 shows the test results of the nuclear magnetic resonance carbon spectrum of the VI type crystal of Compound A. The results are as follows: 13A total of 21 carbon signals have been shown to be present in the C-NMR spectrum, which, in combination with DEPT, shows the presence of four methylene carbons, nine methenyl carbons, and eight carbons not bonded to hydrogen. The carbon signals of all the above hydrogen-bonded carbons were assigned by HSQC data (Table 3.6-5), and the remaining non-hydrogen-bonded carbons were assigned by chemical shift and HMBC: In the HMBC spectrum, δC 164.27 is associated with NH-8, H-11, and H-14, and is assigned to C-9 together with its chemical shift; δC 156.90 is associated with H-11, H-14, and is assigned to C-13; δC 154.16 is associated with H-11 and H-16, and is assigned to C-15; δC 149.11 is associated with H-11, and is assigned to C-14; δC 145.35 and δC 138.98 are associated with H-2, 6, H-3, and 5, and are assigned to C-1 and C-4 together with their chemical shifts, respectively; δC 128.32, 125.47, 122.62 were assigned to C-7 based on peak shape and coupling constant (t, J=285 Hz); δC 119.18 was associated with H-14 and assigned to C-10; δC 116.48 was associated with H-14 and H-16 and assigned to C-12. This carbon spectral data is consistent with the structure of Compound A.
[0459] [Table 48]
[0460] 19 F-NMR and HF NOESY spectra
[0461] FIG. 12 shows the VI type crystal of compound A. 19 FIG. 13 shows the NMR HF NOESY spectrum of the VI type crystal of Compound A. Table 4.6-4 shows the VI type crystal of Compound A. 19Examination of the F-NMR and HF NOESY spectra shows that in the HF NOESY spectrum, the chemical shift at δ -24.72 is associated with H-2, 6 and assigned to F2-7, and δ -177.25 is associated with H-19b, H-20 and H-21 and assigned to F-20. The F and HF NOESY spectra are consistent with the structure of compound A.
[0462] [Table 49]
[0463] HSQC and HMBC spectra
[0464] FIG. 14 shows the NMR HSQC spectrum of the VI crystal of Compound A, FIG. 15 shows the NMR HMBC spectrum of the VI crystal of Compound A, and Table 4.6-5 shows the test results of the HSQC and HMBC spectrum of the VI crystal of Compound A. The results show that in the HMBC spectrum, H-11 is associated with C-9, C-13, C-14, and C-15, H-14 is associated with C-9, C-10, and C-13, H-16 is associated with C-12 and C-15, H-17 is associated with C-15 and C-18, H-18 is associated with C-12 and C-15, and H-19a is associated with C-16 and C-17. H-19b is associated with C-20 and C-22, H-20 is associated with C-19 and C-22, H-21 is associated with C-19 and C-20, and H-22 is associated with C-13, C-19, C-20 and C-21, consistent with the presence of fragment B in the structure; H-2, 6, H-3, 5 are associated with C-1, C-4, and the chemical shifts and molecular formula (C 21 H 17 ClF3N5O2) was consistent with the presence of fragment A in the structure. HSQC and HMBC data were consistent with the structure of compound A.
[0465] [Table 50]
[0466] COSY and NOESY Spectra
[0467] FIG. 16 shows the NMR COSY spectrum of the VI crystal of compound A, FIG. 17 shows the NMR NOESY spectrum of the VI crystal of compound A, and Table 4.6-6 shows the test results of the COSY and NOESY spectrum of the VI crystal of compound A. The results show that in the COSY spectrum, H-17 is related to H-18, H-20 is related to H-19a and H-21, and H-22 is related to H-21, further proving the presence of fragment B in the structure; H-2,6 is related to H-3,5, further proving the presence of fragment A in the structure. In the NOESY spectrum, NH-8 is related to H-3,5, which suggests that C-4 of fragment A is bonded to N-8 of fragment B. The COSY and NOESY spectrum data were consistent with the structure of compound A.
[0468] [Table 51]
[0469] MS analysis
[0470] Equipment and Instrumentation: Waters Acquity Xevo G2-XS QTof UPLC / MS Ultra-high performance liquid chromatography coupled to high-resolution mass spectrometry
[0471] Figure 18 shows the mass spectrum of the VI type crystal of Compound A. As a result, the mass-to-charge ratio of the ion peak displayed in the high-resolution mass spectrum is 464.1102 [M+H] + The deviation from the theoretical value is less than 5 ppm (theoretical value 464.1101, C 21 H 18ClF3N5O2), which has the molecular formula C 21 H 17 ClF3N5O2, which is consistent with the structure of compound A.
[0472] UV analysis
[0473] Instruments and equipment: UV-2600 UV-Vis spectrophotometer (Shimadzu Corporation, Japan)
[0474] Sample analysis: 24.59 mg of a sample of the VI type crystal of Compound A was accurately weighed and dissolved in methanol. The solution was adjusted to 100 mL and mixed well. 1.0 mL of the resulting solution was added to a 25 mL volumetric flask, diluted to a constant volume, and mixed well.
[0475] Figure 19 shows the UV spectrum of the VI type crystal of compound A. Table 4.6-7 shows the UV test results of the VI type crystal of compound A. The absorption peaks at λmax 306, 263 and 201 nm observed in the methanol solution are the π-π* transition absorption peaks of the long chain conjugated system and substituted benzene ring of compound A, which is consistent with the structure of compound A.
[0476] [Table 52]
[0477] DSC and TGA thermal analysis
[0478] Figure 20 shows the DSC curve of the VI crystal of Compound A obtained by General Method 3. In the DSC, it was observed that the melting endothermic peak was at 174.95°C with an onset temperature of 174.20°C, indicating that the melting point of the VI crystal of Compound A is 175°C. As shown in Figure 3, the VI crystal of Compound A remains unchanged after the DVS test.
[0479] Figure 21 shows the TGA curve of the VI crystals of Compound A obtained by General Method 4. In the TGA, a weight loss of 0.003174% was observed before 200°C, indicating that the VI crystals do not contain water of crystallization.
[0480] DVS analysis
[0481] 22 shows the DVS curves of the VI crystals of Compound A obtained by General Method 6. The DVS analysis shows that the water absorption rate is 0.1389% under 10% RH conditions, 1.1852% under 0-80% RH conditions, and 1.7452% under 0-90% RH conditions.
[0482] IR analysis
[0483] Instrumentation and equipment: Nicolet iS10 Fourier transform infrared spectrometer (Thermo)
[0484] Sample analysis: 303.12 mg of potassium bromide and 3.61 mg of a sample of the VI type crystal of Compound A were weighed and mixed thoroughly. The mixture was pulverized to obtain a powder. The KBr tableting method was used, and a polystyrene film was used for correction. The infrared spectrum of this product was 4000-400 cm -1 The data was obtained within the infrared range of 100 MHz.
[0485] Figure 23 shows the IR spectrum of the VI crystal of Compound A. Table 4.6-8 shows the IR test results of the VI crystal of Compound A. In the IR, the following was observed: 3293 cm- 1 shows NH stretching vibration absorption, which indicates that the structure contains an NH moiety; 1661 cm -1 shows a C=O stretching vibration absorption peak, which indicates that the structure contains a C=O moiety; 1599 cm -1 , 1491cm -1 shows the stretching vibration absorption peak of the C=C double bond at 1062 cm -1 , 1020cm -1 shows an in-plane bending vibration absorption peak of =CH at 853 cm-1 shows an out-of-plane bending vibration absorption peak of =CH, indicating that the structure contains a C=C moiety; 1466 cm -1 , 1408cm -1 shows a bending vibration absorption peak of the C-H bond, which indicates that the structure contains CH and C-H moieties; -1 shows the stretching vibration absorption peak of the COC bond, indicating that the structure contains a COC moiety. The infrared spectral characteristics are consistent with the structure of compound A.
[0486] [Table 53]
[0487] Example 4.7 Characterization of Crystalline Form VII of Compound A
[0488] Form VII crystals of Compound A were obtained by suspension crystal conversion in a single solvent of toluene according to the method of Example 3.2, and were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0489] XRPD analysis
[0490] Figure 24 shows the XRPD data for crystalline Form VII of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is provided in Table 4.7.
[0491] [Table 54]
[0492] PLM analysis
[0493] The collected Form VII crystals of Compound A were subjected to PLM analysis by general method 2. The sample was observed to be microcrystalline.
[0494] 1 H NMR analysis
[0495] Compound A VII crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.90 - 7.84 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.6 Hz, 1H), 3.58 - 3.46 (m, 1H), 3.37 (s, 2H), 3.21 (t, J = 9.5 Hz, 1H), 2.15 - 1.97 (m, 2H).
[0496] DSC and TGA thermal analysis
[0497] The collected Form VII crystals of Compound A were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 173.61°C with an onset temperature of 172.39°C.
[0498] The collected Form VII crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed a weight loss of about 3.4% before 200°C.
[0499] 1 H NMR, DSC and TGA analyses showed that Form VII of Compound A was a hydrate.
[0500] Example 4.8 Characterization of Crystalline Form VIII of Compound A
[0501] Following the method of Example 3.3, crystalline form VIII of Compound A was obtained by evaporation in a single ethanol solvent, and analyzed by XRPD, PLM and 1 Characterized by H NMR, the specific results are as follows:
[0502] XRPD analysis
[0503] Figure 25 shows the XRPD data for crystalline Form VIII of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is provided in Table 4.8.
[0504] [Table 55]
[0505] PLM analysis
[0506] The collected Form VIII crystals of Compound A were subjected to PLM analysis by general method 2. The sample was observed to be microcrystalline.
[0507] 1 H NMR analysis
[0508] Compound A VIII crystal 1 The H NMR data is as follows: 1H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.91 - 7.84 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.3 Hz, 1H), 3.58 - 3.48 (m, 1H), 3.35 (s, 2H), 3.21 (t, J = 9.3 Hz, 1H), 2.13 - 1.98 (m, 2H).
[0509] Example 4.9 Characterization of Form IX Crystals of Compound A
[0510] According to the method of Example 3.4, the IX-type crystal of Compound A was obtained by dissolution-precipitation crystallization in tetrahydrofuran / isopropanol, and the crystals were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0511] XRPD analysis
[0512] Figure 26 shows the XRPD data for crystalline Form IX of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is shown in Table 4.9.
[0513] [Table 56-1] [Table 56-2]
[0514] PLM analysis
[0515] The collected Form IX crystals of Compound A were subjected to PLM analysis by General Method 2. The sample was observed to be microcrystalline.
[0516] 1 H NMR analysis
[0517] Compound A IX type crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.91 - 7.84 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.4 Hz, 1H), 3.56 - 3.44 (m, 1H), 3.36 (d, J = 6.7 Hz, 2H), 3.21 (t, J = 9.5 Hz, 1H), 2.14 - 1.96 (m, 2H).
[0518] DSC and TGA thermal analysis
[0519] The collected Form IX crystals of Compound A were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 173.92°C with an onset temperature of 172.14°C.
[0520] Form IX crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed a weight loss of about 5.8% before 200°C.
[0521] 1 H NMR, DSC and TGA analyses showed that Form IX of Compound A was a solvate of tetrahydrofuran, ethanol and isopropanol.
[0522] Example 4.10 Characterization of Type X Crystals of Compound A
[0523] According to the method of Example 3.4, the X-type crystal of compound A was obtained by dissolution-precipitation crystallization in tetrahydrofuran / water, and the crystals were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0524] XRPD analysis
[0525] Figure 27 shows the XRPD data for crystalline Form X of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is provided in Table 4.10.
[0526] [Table 57]
[0527] PLM analysis
[0528] The collected compound A Form X crystals were subjected to PLM analysis by general method 2. The sample was observed to be microcrystalline.
[0529] 1 H NMR analysis
[0530] X-type crystal of compound A 1 The H NMR data is as follows: 1H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.4 Hz, 1H), 7.91 - 7.83 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.23 (s, 1H), 3.58 - 3.47 (m, 1H), 3.36 (d, J = 6.7 Hz, 2H), 3.21 (t, J = 9.4 Hz, 1H), 2.04 (dd, J = 42.1, 12.2 Hz, 2H).
[0531] DSC and TGA thermal analysis
[0532] The collected Compound A Form X crystals were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 172.54° with an onset temperature of 171.38°C.
[0533] Form X crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed a weight loss of about 3.6% before 200°C.
[0534] 1 1 H NMR, DSC and TGA analyses showed that Form X of Compound A was a solvate of tetrahydrofuran.
[0535] Example 4.11 Characterization of Form XI Crystals of Compound A
[0536] According to the method of Example 3.5, the XI type crystal of Compound A was obtained by cooling crystallization in acetonitrile, and the crystals were analyzed by XRPD, PLM, 1 It was characterized by H NMR, DSC and TGA, with the specific results being as follows:
[0537] XRPD analysis
[0538] Figure 28 shows the XRPD data for crystalline Form XI of Compound A obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ± 0.2°2θ is provided in Table 4.11.
[0539] [Table 58-1] [Table 58-2]
[0540] PLM analysis
[0541] The collected Form XI crystals of Compound A were subjected to PLM analysis by general method 2. The sample was observed to be microcrystalline.
[0542] 1 H NMR analysis
[0543] Compound A XI type crystal 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.84 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.24 (d, J = 2.3 Hz, 1H), 7.91 - 7.83 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.2 Hz, 1H), 3.58 - 3.45 (m, 1H), 3.36 (d, J = 6.7 Hz, 2H), 3.21 (t, J = 9.4 Hz, 1H), 2.16 - 1.92 (m, 2H).
[0544] DSC and TGA Thermal Analysis
[0545] The collected Form XI crystals of Compound A were subjected to DSC analysis by General Method 4. DSC analysis showed a melting endotherm peak at 174.45°C with an onset temperature of 172.7°C.
[0546] Form XI crystals of Compound A were subjected to TGA analysis by General Method 5. The TGA analysis showed a weight loss of about 3.9% before 200°C.
[0547] 1 H NMR, DSC and TGA analyses showed that Form XI crystals of Compound A were a solvate of acetonitrile.
[0548] Example 5. Grinding Study of Compound A Forms III, VI, and VII Specific amounts of the III, VI, and VII forms of compound A were added to a mortar and ground at room temperature. The solid-state XRPD before and after grinding was compared.
[0549] The XRPD results showed that after milling, the crystallinity of the VI crystals (anhydrous crystals) was slightly decreased, and the III crystals (hydrate) and the VII crystals (hydrate) were changed to amorphous form, as shown in FIG.
[0550] Example 6 Preparation of a crystalline salt of Compound A Initial attempts to prepare crystalline salts of Compound A using Compound A Form I crystals as starting material consisted of two phases. The first phase included solubility studies of the starting material and salt formation screening in 96-well plates. In the second phase, potential crystalline salts were prepared on a milligram scale. These initial attempts identified five crystalline salt forms of Compound A: Compound A hydrochloride Form I, Compound A hydrobromide Form I, Compound A mesylate Form I, Compound A p-toluenesulfonate Form I and II, and Compound A benzenesulfonate Form I.
[0551] Example 6.1 Solubility Study of Starting Material (Form I Crystals of Compound A)
[0552] Approximately 2 mg of the starting material was weighed out and added to a sample bottle and various solvents were added respectively until the starting material was dissolved. The solubility results are shown in Table 6.1. The results show that the starting material has good solubility in tetrahydrofuran, acetone, 2-butanone, acetonitrile and ethyl acetate.
[0553] [Table 59]
[0554] Example 6.2 Salt-Forming Screening in 96-Well Plates
[0555] Eight acid solutions with a concentration of 0.1 M were prepared by dissolving specific amounts of hydrochloric acid, hydrobromic acid, sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, benzenesulfonic acid, maleic acid and phosphoric acid in 10 mL of methanol, respectively. A solution of starting material with a concentration of 30 mg / mL was prepared by dissolving 364.3 mg of starting material in acetone and diluting this solution to 12 mL with acetone. This 30 mg / mL solution of starting material was dispensed in a volume of 100 μL per well in a 96-well plate. Then, the eight acid solutions prepared above were added to each row of wells in a volume of 65 μL (sulfuric acid was 33 μL) per well. After complete evaporation of the solvent, 200 μL of solvent (salt forming solvents were methanol, ethanol, isopropanol, 2-butanone, isobutanol, tetrahydrofuran, acetonitrile, methyl tert-butyl ether, acetone, water, ethyl acetate and isopropyl acetate) was added to each well. The solution was sealed with a perforated sealing film and allowed to evaporate to dryness at room temperature in a fume hood. One sample was selected from each column. 1 H NMR testing was performed to determine if a salt was formed. XRPD testing was performed on the solid sample to determine if the solid was a crystalline form.
[0556] 1H NMR results showed that the samples obtained by reacting the free base of Compound A with hydrochloric acid, hydrobromic acid, methanesulfonic acid, p-toluenesulfonic acid, and benzenesulfonic acid had chemical shifts. XRPD results showed that the samples obtained by reaction with the above acids were crystalline. The results are shown in Table 6.2.
[0557] [Table 60]
[0558] Example 6.3 Small-scale preparation of Form I crystals of the hydrochloride salt of Compound A
[0559] Approximately 30 mg of starting material (form I crystals of compound A) was weighed and dissolved in various volumes of five solvents (acetone, ethyl acetate, acetonitrile, 2-butanone and isopropyl acetate) to form solutions. 5.93 μL or 16 μL of concentrated hydrochloric acid was added to each solution and stirred at room temperature for half an hour. Solids precipitated from all solutions. The mixtures were stirred for an additional 30 minutes and then filtered. The reaction conditions and results are listed in Table 6.3. XRPD results showed that hydrochloride salt crystals were prepared.
[0560] [Table 61]
[0561] Example 6.4 Small-scale preparation of Form I crystals of the benzenesulfonate salt of Compound A
[0562] Approximately 30 mg of starting material (form I crystals of compound A) was weighed and dissolved in various volumes of five solvents (acetone, ethyl acetate, acetonitrile, 2-butanone and isopropyl acetate) to form solutions. Approximately 13 mg of benzenesulfonic acid was added to each solution and the mixture was stirred at room temperature for half an hour. Solids precipitated from all solutions. The mixture was stirred for an additional 30 minutes and then filtered. The reaction conditions and results are listed in Table 6.4. XRPD results showed that benzenesulfonate salt crystals were prepared.
[0563] [Table 62]
[0564] Example 6.5 Small-scale preparation of Form I and Form II crystals of the p-toluenesulfonate salt of Compound A
[0565] Approximately 30 mg of starting material (form I crystals of compound A) was weighed and dissolved in various volumes of five solvents (acetone, ethyl acetate, acetonitrile, 2-butanone and isopropyl acetate) to form solutions. Approximately 13 mL of a 1 M solution of p-toluenesulfonic acid in methanol was added to each solution and the mixture was stirred at room temperature for half an hour. Solids precipitated out of all the solutions. The mixture was stirred for an additional 30 minutes and then filtered. The reaction conditions and results are shown in Table 6.5. XRPD results showed that two forms of crystals, named form I crystals of p-toluenesulfonic acid and form II crystals of p-toluenesulfonic acid, were prepared.
[0566] [Table 63]
[0567] Example 6.6 Enlarged preparation of Form I crystals of p-toluenesulfonate salt of Compound A
[0568] At room temperature, 500.1 mg of the starting material (Form I crystals of Compound A) was added to 5 mL of acetone, followed by 1.1 mL of a 1 M solution of p-toluenesulfonic acid in methanol. After stirring for 3 minutes, a solid formed. After stirring for an additional 40 minutes, the mixture was filtered and dried overnight at 50° C. A total of 407.1 mg of salt was obtained with a yield of 81.4%. The results obtained are listed in Table 6.6.
[0569] [Table 64]
[0570] Example 6.7 Small-scale preparation of Form I crystals of the mesylate salt of Compound A
[0571] Approximately 40.1 mg of starting material (Form I crystals of Compound A) was weighed and dissolved in 300 μL of acetone to form a solution. Approximately 14 μL of methanesulfonic acid was then added and the mixture was stirred at room temperature for 1 minute. A solid precipitated out of the solution. The mixture was stirred for an additional 30 minutes and then filtered. The resulting solid was left at 50° C. overnight and then characterized. The reaction conditions and results are listed in Table 6.7.
[0572] [Table 65]
[0573] Example 6.8 Small-scale preparation of Form I crystals of the hydrobromide salt of Compound A
[0574] Approximately 31.2 mg of starting material (Form I crystals of Compound A) was weighed and dissolved in 300 μL of acetone to form a solution. Then, approximately 670 μL of a 0.1 M solution of hydrobromic acid in methanol was added, and the mixture was stirred at room temperature for 1 hour. No solid precipitated. The mixture was purged with nitrogen gas to dryness, resulting in an oil. 300 μL of MTBE was added. The mixture was stirred for 1 hour and then filtered. The resulting solid was left at 50° C. overnight and then characterized. The reaction conditions and results are listed in Table 6.8.
[0575] [Table 66]
[0576] Example 7 Characterization of the Crystalline Salt of Compound A Example 7.1 Characterization of Crystalline Form I of the Hydrochloride Salt of Compound A
[0577] XRPD analysis
[0578] Figure 31 shows the XRPD data for crystalline Form I of Compound A hydrochloride obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ (°2θ) ±0.2°2θ is provided in Table 7.1.
[0579] [Table 67]
[0580] PLM analysis
[0581] Collected Form I crystals of the hydrochloride salt of Compound A, prepared according to the method of Example 6.3, were subjected to PLM analysis by General Method 2. Both the HCl-S1 and HCl-S2 batch samples were observed to be crystalline with irregular sheet-like particles.
[0582] 1 H NMR analysis
[0583] Form I crystals of the hydrochloride salt of Compound A from the HCl-S1 batch prepared by the method of Example 6.3 1 H NMR is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.49 (s, 1H), 8.95 (d, J = 1.4 Hz, 1H), 8.86 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.67 (d, J = 3.54 (ddd, J = 39.4, 13.3, 3.0 Hz, 1H), 3.34 (dt, J = 12.2, 9.0 Hz, 2H), 3.25 (t, J = 9.5 Hz, 1H), 2.19 - 1.94 (m, 2H).
[0584] Compound A type I crystal 1 H NMR is as follows: 1H NMR (300 MHz, DMSO-d6) δ 10.27 (s, 1H), 8.90 (d, J = 1.4 Hz, 1H), 8.84 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.65 (d, J = 2.6 Hz, 1H), 8.25 (d, J = 2.3 Hz, 1H), 7.93 - 7.79 (m, 2H), 7.35 (d, J = 9.0 Hz, 2H), 5.30 (d, J = 53.4 Hz, 1H), 3.63 - 3.45 (m, 1H), 3.41 - 3.34 (m, 2H), 3.27 - 3.18 (m, 1H), 2.20 - 1.87 (m, 2H).
[0585] Compound A type I crystal 1 When compared with H NMR, the crystals of the hydrochloride salt of Compound A were 1 1 H NMR had chemical shifts that confirmed it to be the salt form.
[0586] DSC and TGA thermal analysis
[0587] Form I crystals of the hydrochloride salt of Compound A collected from the HCl-S1 batch prepared according to the method of Example 6.3 were subjected to DSC analysis by General Method 4. In DSC, a sample of Form I crystals of the hydrochloride salt of Compound A showed a melting endotherm peak at 229.41°C with an onset temperature of 209.08°C.
[0588] Form I crystals of the hydrochloride salt of Compound A collected from the HCl-S1 batch were subjected to TGA analysis by General Method 5. In TGA, the Form I crystals of the hydrochloride salt of Compound A sample has a weight loss of 0.6752% before 175°C.
[0589] DSC and TGA analyses showed that Form I crystals of the hydrochloride salt of Compound A were anhydrous crystals.
[0590] DVS analysis
[0591] Figure 32 shows the DVS curve of the Form I crystals of the hydrochloride salt of Compound A from the HCl-S1 batch prepared according to the method of Example 6.3 obtained by General Method 6. In the DVS, the sample of the Form I crystals of the hydrochloride salt of Compound A was slightly hygroscopic. As shown in Figure 32, the water absorption rate was about 0.4% under the condition of 0-40% RH (relative humidity) and about 2.8% under the condition of 0-90% RH.
[0592] Crystalline Form I of the hydrochloride salt of Compound A was unchanged after the sample was tested by DVS, as shown in FIG.
[0593] Example 7.2 Characterization of Form I Crystals of the Benzenesulfonate Salt of Compound A
[0594] XRPD analysis
[0595] Figure 34 shows XRPD data for Form I crystals of the benzenesulfonate salt of Compound A from batch PhSO3H-S1 of Example 6.4, obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ±0.2 °2θ is provided in Table 7.2.
[0596] [Table 68]
[0597] PLM analysis
[0598] Form I crystals of the benzenesulfonate salt of Compound A from the PhSO3H-S1 batch in Example 6.4 were subjected to PLM analysis by general method 2. The sample from the PhSO3H-S1 batch was observed to contain a mixture of irregular sheet-like particles and a small amount of needle-like crystals.
[0599] 1 H NMR analysis
[0600] Form I crystals of benzenesulfonate salt of Compound A from the PhSO3H-S1 batch in Example 6.41 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.29 (s, 1H), 8.91 (d, J = 1.5 Hz, 1H), 8.83 (d, J = 2.4 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.66 (d, J = 2.6 Hz, 1H), 8.26 (d, J = 2.3 Hz, 1H), 7.91 - 7.83 (m, 2H), 7.59 (dd, J = 7.6, 2.0 Hz, 2H), 7.35 (d, J = 9.0 Hz, 2H), 7.32 - 7.30 (m, 3H), 5.30 (d, J = 53.4 Hz, 1H), 3.52 (ddd, J = 39.4, 13.2, 3.1 Hz, 1H), 3.39 - 3.26 (m, 2H), 3.22 (t, J = 9.3 Hz, 1H), 2.03 (dd, J = 54.1, 12.1 Hz, 2H).
[0601] Compound A type I crystal 1 Comparing with the H NMR results, the I-form crystal of benzenesulfonic acid of compound A 1 1 H NMR results showed that this batch had chemical shifts that indicated a 1:1 ratio of free base to benzenesulfonic acid.
[0602] DSC and TGA thermal analysis
[0603] Form I crystals of the benzenesulfonate salt of Compound A collected from the PhSO3H-S1 batch of Example 6.4 were subjected to DSC analysis by General Method 4. In the DSC, the Form I crystals of the benzenesulfonate salt of Compound A were shown to have a narrow melting endotherm peak at 252.81 °C with an onset temperature of 252.22 °C.
[0604] The type I crystals of Compound A benzenesulfonate salt recovered from the PhSO3H-S1 batch were subjected to TGA analysis by General Method 5. In TGA, the type I crystals of Compound A benzenesulfonate salt sample had a weight loss of 0.4773% before 200°C.
[0605] DSC and TGA analyses showed that Form I crystals of the benzenesulfonate salt of Compound A were anhydrous crystals.
[0606] DVS analysis
[0607] 35 shows the DVS curve of the type I crystals of benzenesulfonate salt of Compound A of the PhSO3H-S1 batch in Example 6.4 obtained by General Method 6. In the DVS, the type I crystals of benzenesulfonate salt of Compound A were slightly hygroscopic, with the water absorption rate being about 0.4% under 0-60% RH conditions and about 1.5% under 0-90% RH conditions.
[0608] Crystalline Form I of the benzenesulfonate salt of Compound A was unchanged after the sample was tested by DVS, as shown in FIG.
[0609] Example 7.3 Characterization of Form I Crystals of p-Toluenesulfonate Salt of Compound A
[0610] XRPD analysis
[0611] Figure 37 shows XRPD data for crystalline Form I of the p-toluenesulfonate salt of Compound A from batch PTAS-S1 of Example 6.5, obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ± 0.2 °2θ is provided in Table 7.3.
[0612] [Table 69]
[0613] PLM analysis
[0614] Form I crystals of the p-toluenesulfonate salt of Compound A from the PTSA-S1 batch of Example 6.5 were subjected to PLM analysis by general method 2. The sample from this batch was observed to be needle-like crystals.
[0615] 1 H NMR analysis
[0616] Form I crystals of p-toluenesulfonate of Compound A from the PTSA-S1 batch of Example 6.5 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.29 (s, 1H), 8.91 (d, J = 1.5 Hz, 1H), 8.83 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.66 (d, J = 2.6 Hz, 1H), 8.26 (d, J = 2.3 Hz, 1H), 7.91 - 7.84 (m, 2H), 7.47 (d, J = 8.1 Hz, 2H), 7.35 (d, J = 9.1 Hz, 2H), 7.11 (d, J = 7.8 Hz, 2H), 5.30 (d, J = 53.2 Hz, 1H), 3.52 (ddd, J = 39.7, 13.4, 3.2 Hz, 1H), 3.32 (dt, J = 22.8, 9.3 Hz, 2H), 3.23 (t, J = 9.6 Hz, 1H), 2.29 (s, 3H), 2.15 - 1.93 (m, 2H).
[0617] Compound A type I crystal 1 Comparing with the H NMR results, the I-form crystals of p-toluenesulfonic acid of compound A 1 1 H NMR results show that this batch has chemical shifts and a 1:1 ratio of free base to p-toluenesulfonate salt.
[0618] DSC and TGA thermal analysis
[0619] Form I crystals of p-toluenesulfonate salt of Compound A collected from the PTSA-S1 batch of Example 6.5 were subjected to DSC analysis by General Method 4. In the DSC, the Form I crystals of p-toluenesulfonate salt of Compound A were shown to have a narrow melting endotherm peak at 236.18°C with an onset temperature of 234.56°C.
[0620] The type I crystals of p-toluenesulfonate salt of Compound A collected from the PTSA-S1 batch were subjected to TGA analysis by General Method 5. In TGA, the type I crystals of p-toluenesulfonate salt of Compound A had a weight loss of 0.1415% before 200°C.
[0621] DSC and TGA analyses showed that Form I crystals of p-toluenesulfonate of Compound A were anhydrous crystals.
[0622] DVS analysis
[0623] 38 shows the DVS curves of the Type I crystals of p-toluenesulfonate of Compound A from the PTSA-S1 batch of Example 6.5 obtained by General Method 6. In the DVS, the Type I crystals of p-toluenesulfonate of Compound A were slightly hygroscopic, with the water absorption rate being about 0.39% under 0-80% RH conditions and about 0.61% under 0-90% RH conditions.
[0624] Crystalline Form I of the p-toluenesulfonate salt of Compound A was unchanged after the sample was tested with DVS, as shown in FIG.
[0625] Example 7.4 Characterization of Form II Crystals of p-Toluenesulfonate Salt of Compound A
[0626] XRPD analysis
[0627] Figure 40 shows XRPD data for crystalline Form II of the p-toluenesulfonate salt of Compound A from the PTAS-S2 batch of Example 6.5, obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ± 0.2 °2θ is provided in Table 7.4.
[0628] [Table 70]
[0629] PLM analysis
[0630] Crystalline Form II of the p-toluenesulfonate salt of Compound A collected from the PTSA-S2 batch of Example 6.5 was subjected to PLM analysis by general method 2. The sample from this batch was observed to be irregularly crystalline.
[0631] 1 H NMR analysis
[0632] Form II crystals of p-toluenesulfonate of Compound A from the PTSA-S2 batch of Example 6.5 1 The H NMR data is as follows: 1H NMR (400 MHz, DMSO-d6) δ 10.30 (s, 1H), 8.91 (d, J = 1.2 Hz, 1H), 8.83 (d, J = 2.2 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.66 (d, J = 2.5 Hz, 1H), 8.27 (s, 1H), 7.92 - 7.83 (m, 2H), 7.48 (d, J = 8.0 Hz, 2H), 7.35 (d, J = 9.1 Hz, 2H), 7.12 (d, J = 7.9 Hz, 2H), 5.30 (d, J = 53.2 Hz, 1H), 3.60 - 3.44 (m, 1H), 3.39 - 3.29 (m, 2H), 3.23 (t, J = 9.5 Hz, 1H), 2.29 (s, 3H), 2.17 - 1.94 (m, 2H).
[0633] Compound A type I crystal 1 H NMR of the p-toluenesulfonate salt of Compound A in Form II crystals 1 1 H NMR results for this batch have chemical shifts indicating a 1:1 ratio of free base to p-toluenesulfonate salt.
[0634] DSC and TGA thermal analysis
[0635] Crystalline Form II of the p-toluenesulfonate salt of Compound A collected from the PTSA-S2 batch of Example 6.5 was subjected to DSC analysis by General Method 4. In the DSC, the sample of crystalline Form II of the p-toluenesulfonate salt of Compound A was shown to have a narrow melting endotherm peak at 234.45° C. with an onset temperature of 232.18.
[0636] Form II crystals of p-toluenesulfonate salt of Compound A collected from the PTSA-S2 batch of Example 6.5 were subjected to TGA analysis by General Method 5. In TGA, the sample of Form II crystals of p-toluenesulfonate salt of Compound A had a weight loss of 0.2437% before 200°C.
[0637] DSC and TGA analyses showed that Form II crystals of p-toluenesulfonate of Compound A were anhydrous crystals.
[0638] Example 7.5 Characterization of Form I Crystals of the Mesylate Salt of Compound A
[0639] XRPD analysis
[0640] Figure 41 shows XRPD data for Form I crystals of the mesylate salt of Compound A from batch CH3SO3H-S1 of Example 6.7, obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ± 0.2°2θ is provided in Table 7.5.
[0641] [Table 71]
[0642] PLM analysis
[0643] Form I crystals of the mesylate salt of Compound A taken from batch CH3SO3H-S1 in Example 6.7 were subjected to PLM analysis by general method 2. The sample from this batch was observed to be irregularly crystalline.
[0644] 1 H NMR analysis
[0645] Form I crystals of mesylate of Compound A from batch CH3SO3H-S1 of Example 6.7 1 The H NMR data is as follows: 1H NMR (400 MHz, DMSO-d6) δ 10.29 (s, 1H), 8.90 (d, J = 1.5 Hz, 1H), 8.83 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.6, 1.5 Hz, 1H), 8.66 (d, J = 2.6 Hz, 1H), 8.26 (d, J = 2.3 Hz, 1H), 7.91 - 7.83 (m, 2H), 7.35 (d, J = 9.1 Hz, 2H), 5.30 (d, J = 53.4 Hz, 1H), 3.52 (ddd, J = 39.9, 13.6, 3.3 Hz, 1H), 3.38 - 3.27 (m, 2H), 3.22 (t, J = 9.5 Hz, 1H), 2.34 (d, J = 1.4 Hz, 3H), 2.03 (dd, J = 54.4, 11.6 Hz, 2H).
[0646] Compound A type I crystal 1 When compared with the H NMR results, the crystals of the mesylate salt of Compound A were 1 1 H NMR results for this batch have chemical shifts indicating a 1:2 ratio of free base to mesylate salt.
[0647] DSC and TGA thermal analysis
[0648] Form I crystals of Compound A mesylate salt collected from batch CHSOH-S1 in Example 6.7 were subjected to DSC analysis by General Method 4. DSC showed that Form I crystals of Compound A mesylate salt had a narrow melting endotherm peak at 206.37°C with an onset temperature of 204.41°C.
[0649] Form I crystals of Compound A mesylate salt collected from batch CHSOH-S1 in Example 6.7 were subjected to TGA analysis by General Method 5. In TGA, the sample of Form I crystals of Compound A mesylate salt had a weight loss of 0.6541% before 200°C.
[0650] DSC and TGA analyses showed that Form I crystals of the mesylate salt of Compound A were anhydrous crystals.
[0651] DVS analysis
[0652] 42 shows the DVS curve of the Form I crystals of Compound A mesylate from the CH3SO3H-S1 batch in Example 6.7 obtained by General Method 6. In the DVS, the sample of Form I crystals of Compound A mesylate was hygroscopic, with the water absorption rate being about 3.6% under 0-80% RH conditions and about 40.3% under 0-90% RH conditions.
[0653] Crystalline Form I of the mesylate salt of Compound A was unchanged after the sample was tested by DVS, as shown in FIG.
[0654] Example 7.6 Characterization of Crystalline Form I of the Hydrobromide Salt of Compound A
[0655] XRPD analysis
[0656] Figure 44 shows XRPD data for Form I crystals of the hydrobromide salt of Compound A from batch HBr-S1 of Example 6.8, obtained according to General Method 1. A list of the XRPD peaks and their relative intensities at diffraction angles 2θ degrees (°2θ) ±0.2 °2θ is provided in Table 7.6.
[0657] [Table 72]
[0658] PLM analysis
[0659] Form I crystals of the hydrobromide salt of Compound A taken from the HBr-S1 batch of Example 6.8 were subjected to PLM analysis by general method 2. The sample from this batch was observed to be irregularly crystalline.
[0660] 1 H NMR analysis
[0661] Form I crystals of the hydrobromide salt of Compound A from the HBr-S1 batch of Example 6.8 1 The H NMR data is as follows: 1 H NMR (400 MHz, DMSO-d6) δ 10.30 (s, 1H), 8.91 (d, J = 1.5 Hz, 1H), 8.83 (d, J = 2.3 Hz, 1H), 8.75 (dd, J = 2.5, 1.5 Hz, 1H), 8.66 (d, J = 3.52 (ddd, J = 39.5, 13.3, 3.1 Hz, 1H), 3.32 (dt, J = 18.3, 10.0 Hz, 2H), 3.23 (t, J = 9.5 Hz, 1H), 2.17 - 1.94 (m, 2H).
[0662] Compound A type I crystal 1 Comparing with the H NMR results, the crystals of the hydrobromide salt of Compound A in type I form are 1 1 H NMR results show that this batch has the chemical shifts:
[0663] DSC and TGA thermal analysis
[0664] Form I crystals of the hydrobromide salt of Compound A taken from batch HBr-S1 in Example 6.8 were subjected to DSC analysis by General Method 4. In the DSC, the sample of Form I crystals of the hydrobromide salt of Compound A showed a broad melting endothermic peak at 250.54°C with an onset temperature of 240.88°C.
[0665] Form I crystals of the hydrobromide salt of Compound A taken from the HBr-S1 batch in Example 6.8 were subjected to TGA analysis by General Method 5. In TGA, Form I crystals of the hydrobromide salt of Compound A had a weight loss of 0.6011% before 200°C.
[0666] DSC and TGA analyses showed that Form I crystals of the hydrobromide salt of Compound A were anhydrous crystals.
[0667] DVS analysis
[0668] Figure 45 shows the DVS curve of the Form I crystals of the hydrobromide salt of Compound A from the HBr-S1 batch of Example 6.8 obtained by General Method 6. In the DVS, the Form I crystals of the hydrobromide salt of Compound A were slightly hygroscopic, with a water absorption rate of about 0.67% under conditions of 0-80% RH.
[0669] Crystalline Form I of the hydrobromide salt of Compound A was unchanged after the sample was tested with DVS, as shown in FIG.
[0670] Example 8 Stability Study of Form I Crystals of Compound A and Form I Crystals of p-Toluenesulfonate of Compound A A certain amount of the crystals of Compound A type I and the crystals of p-toluenesulfonate salt of Compound A type I (batch number: PTSA-A1) were placed in a stability test chamber and maintained at 40°C / 75%RH and 60°C for 7 days, respectively. HPLC and XRPD tests were performed at various time points. Specific results are listed in Table 8.
[0671] The XRPD results showed that the Form I crystals of Compound A and the Form I crystals of the p-toluenesulfonate salt of Compound A remained unchanged at 40° C. / 75% RH and 60° C. for 7 days, as shown in FIG. 29 and FIG. 47.
[0672] [Table 73]
[0673] Example 9 Solubility Study of Form I Crystals of Compound A and Form I Crystals of the p-Toluenesulfonate Salt of Compound A in Various Vehicles The solubility of type I crystals of Compound A and type I crystals of the p-toluenesulfonate salt of Compound A in SGF (simulated gastric fluid), FaSSIF (simulated intestinal fluid under fasted conditions) and FeSSIF (simulated intestinal fluid under fasted conditions) was investigated.
[0674] The solubility of samples in SGF, FaSSIF and FeSSIF was measured for 24 hours at 37°C. 40 mg of sample was placed in a sample bottle and 1.5 mL of solvent was added. The mixture was mixed well and shaken at 200 rpm on a shaker for 24 hours. The suspension was filtered at 0.5 hours, 2 hours and 24 hours. The filtrate was analyzed by HPLC and the solid was tested by XRPD. The specific results are listed in Table 9.
[0675] [Table 74]
[0676] The results showed that the solubility of the free base and the p-toluenesulfonate salt was affected by the pH value. The p-toluenesulfonate salt showed higher solubility than the free base in FaSSIF and FeSSIF vehicles at 24 hours. The free base showed higher solubility than the p-toluenesulfonate salt in FeSSIF vehicle at 0.5 and 2 hours. Under other conditions, the solubilities of both were comparable.
[0677] When the I-type crystals of Compound A were dissolved in SGF, FaSSIF, and FeSSIF for 2 hours, the crystal form of the I-type crystals of Compound A changed as shown in FIG. 48, FIG. 49, and FIG.
[0678] When the type I crystals of p-toluenesulfonate of Compound A were dissolved in SGF for 24 hours and in FaSSIF and FeSSIF for 0.5 hours, the crystal form of the type I crystals of p-toluenesulfonate of Compound A changed, as shown in Figures 51, 52, and 53.
[0679] The p-toluenesulfonate salt became more soluble after 2 hours in solutions with higher pH values, which was due to the dissociation of the p-toluenesulfonate salt with increasing pH value.
[0680] Example 10 Single crystal X-ray structure and absolute stereochemistry of compound A Single crystals of compound A were grown by slow evaporation at room temperature. Method 1: Approximately 100 mg of VI crystals of compound A was dissolved in acetone or methanol, respectively, and then anti-solvent n-heptane was added until the solution became slightly cloudy. 1-2 drops of solvent were added or the temperature was increased until the solution became clear again. The above solution was slowly evaporated at room temperature. Method 2: Approximately 100 mg of VI crystals of compound A was dissolved in methanol to prepare a saturated solution, and the above solution was slowly evaporated at room temperature.
[0681] Collection and analysis of single crystal structure data was performed by the Crystallography Laboratory at Peking University. Single crystal diffraction data for the sample was acquired at 180 K using a Rigaku XtaLAB PRO 007HF(Mo) diffractometer with a Mo target Kα spectral line (λ=0.71073 Å). Data correction and absorption correction were performed using the CrysAlisPro program, and the structure was resolved by a dual-space algorithm using the SHELXT program. Non-hydrogen atoms could be located in different Fourier spectra, and hydrogen atoms were geometrically packed to the parent atoms. Final structure refinement was performed using the SHELXL program with F 2 The calculation was based on the full-matrix least squares method.
[0682] A single crystal of compound A was obtained by slowly evaporating it in a methanol solution at room temperature, and its single crystal structure was analyzed. This single crystal was a bulk crystal, and its structural formula was C 21 H 17 The compound was ClF3N5O2·0.5CH3OH, a solvate of methanol. The single crystal belonged to the monoclinic system and C2 space group. The structure of the single crystal is shown in Figure 54. Each unit contained two molecules of compound A and one molecule of methanol, and the main molecule had the same molecular structure as compound A. The crystal structure parameters obtained by decomposition are shown in Table 10.
[0683] [Table 75]
[0684] Example 11 Stability Study of Form VI Crystal of Compound A
[0685] High temperature (60℃), high humidity (25℃ / 92.5%RH), high temperature and high humidity (40℃ / 75%RH), light (visible light 4500Lux ± 500Lux, near ultraviolet 85μw / cm 2 ) under the test conditions, a sample of Compound A VI crystal was placed in an open glass bottle. Samples were taken and tested on days 0, 10, and 30 to study the physical stability of Compound A VI crystal API. The test items were appearance, crystal form, hygroscopic weight gain (measured only under high humidity conditions), content, and related substances. Specific results are listed in Table 11.
[0686] [Table 76]
[0687] The results of the tests on appearance, crystal form and related substances showed that the VI crystal form of Compound A was stable under high temperature (60°C), high humidity (25°C / 92.5%RH), high temperature and high humidity (40°C / 75%RH), and light (visible light 4500 Lux±500 Lux, near ultraviolet light 85μw / cm 2 ) for 30 days and for 10 days under light conditions. Moreover, as shown in Figure 55, the crystal structure remained unchanged.
[0688] Example 12 Dissolution Study of Compound A The present inventors have investigated the effects of adding a solubilizer and a glidant to improve the dissolution of a formulation containing Compound A. It was found that when sodium lauryl sulfate (solubilizer) was added, the dissolution of Compound A in the formulation decreased with increasing amount of sodium lauryl sulfate. However, it was found that the addition of colloidal silica 200 (glidant) could improve the dissolution of Compound A.
[0689] [Table 77]
[0690] [Table 78]
[0691] [Table 79]
[0692] From the above results, it can be seen that with increasing amount of colloidal silica, the dissolution results increase and when the amount of colloidal silica is 3%, the product is completely dissolved. Therefore, 3% colloidal silica 200 was selected as the amount of lubricant for further study.
[0693] Example 13 Representative tablet formulation of VI type crystals of Compound A Immediate release film-coated tablets of 10 mg and 40 mg doses were prepared using a direct powder compression process. The tablet compositions are provided in Table 13.
[0694] [Table 80]
[0695] Tablets of two sizes (10 mg and 40 mg) were prepared using the same batch of blended materials and compressed into tablets of different sizes in equal proportions. The total blended batches (14,000 tablets each) for preparing tablets of 10 mg and 40 mg sizes were used as representative, and the formulation information of the batches is shown in Table 13-2 below.
[0696] [Table 81]
[0697] The method for preparing the tablets is as follows. 1. Adjuvants and API were weighed according to the amount of formulation. 2. Sieving: Compound A type VI crystals were passed through an 80 mesh sieve; lactose monohydrate was passed through a 60 mesh sieve; microcrystalline cellulose and colloidal silica were placed in the same pharmaceutical LDPE bag and passed through a 30 mesh sieve, which was designated as mixture 1; croscarmellose sodium and magnesium stearate were each passed through a 30 mesh sieve. 3. Main mixing: Mixture 1, lactose monohydrate, VI type crystals of Compound A, and croscarmellose sodium were added in sequence to a hopper and mixed at a mixing speed of 15 rpm for a mixing time of 15 minutes. 4. Total mixing: Magnesium stearate was added to a hopper mixer, and total mixing was carried out at a mixing speed of 15 rpm for a mixing time of 5 minutes. 5. Tableting: The punches for 10 mg tablets were 6 mm dimple round punches, and the punches for 40 mg tablets were 10.0 mm dimple round punches. After the equipment test run, the official production was carried out. The tablet weight, hardness and friability were monitored online to ensure that they met the tabletting standards shown in Table 13-3.
[0698] [Table 82] 6. Coating: 12% Opadry coating solution was freshly prepared with purified water. The air inlet temperature was set to 50-60°C, and the coating pan was preheated at a rotation speed of 2 rpm. The coating pan was preheated so that the exhaust temperature was 42°C, the air inlet temperature was set to 50-70°C, the pot rotation speed was set to 5-12 rpm, and the air inlet volume was set to 300±100 m. 3Spray coating was performed with the pump set at 1000 / h. 10 mg tablets: pump flow rate: 8 ml / min - 30 ml / min, atomization pressure: 0.5 ± 0.3 bar, atomization angle control pressure: 1 ± 0.5 bar; 40 mg tablets: pump flow rate: 8 ml / min - 40 ml / min, atomization pressure: 1.5 ± 1 bar, atomization angle control pressure: 1.5 ± 1 bar. Coating parameters and coating weight gain were monitored. When the coating weight gain reached the target range of 2.5 - 3.5%, the spray was stopped, the heat was turned off and the coating pan was adjusted to a rotation speed of 5 rpm and an air inlet rate of 200 - 500 m3 / h. After drying for 5 minutes the product was discharged. 7. Packaging: The 10 mg and 40 mg tablets were packaged in 45 mL and 75 mL oral solid drug high density polyethylene bottles, respectively, containing 30 mg tablets each. 8. Labeling: Labels were applied to the product bottles, one label per bottle.
[0699] Example 14 Chemical Stability Study of Representative Tablet Formulations (I) Chemical stability data after 10 days of exposure to light and stability data at 40°C / 75%RH in open and closed containers were collected on the 10th day and 30th day, respectively, for the 10 mg and 40 mg tablets prepared in Example 13. Dissolution and impurity tests were performed to evaluate the chemical stability of the test formulations. Specific results are shown in Tables 14-1 and 14-2.
[0700] [Table 83]
[0701] The data in the above table show that the dissolution of the tablets does not change over 10 days under light conditions; does not change significantly over 10 and 30 days under accelerated 40°C / 75% RH (open) conditions; and does not change significantly over 10 and 30 days under accelerated 40°C / 75% RH (closed) conditions.
[0702] [Table 84]
[0703] The data in the above table shows that tablets of 10mg and 40mg grades show no increase in impurities for 10 days under light conditions and for 10 and 30 days under accelerated conditions of 40°C / 75%RH (open and closed).
[0704] Example 15 Chemical Stability Study of Representative Tablet Formulations (II) For the 10mg tablets and 40mg tablets prepared in Example 12, stability influencing factors, accelerated stability test and long-term stability test were respectively carried out according to the storage conditions specified in ICH Q1 guideline, and the corresponding results are listed in Tables 15-1, 15-2, 15-3 and 15-4.
[0705] [Table 85]
[0706] [Table 86]
[0707] [Table 87]
[0708] [Table 88]
[0709] The results, as shown in Tables 15-1 and 15-2, showed that there was no significant difference in content, total impurity content, chiral purity and dissolution of the 10 mg and 40 mg tablets under high temperature, high humidity and light conditions.
[0710] The content, total impurity content, dissolution and moisture of the 10 mg and 40 mg tablets did not change significantly within 3 months under accelerated conditions, as shown in Table 15-3.
[0711] As shown in Table 15-4, the content, total impurity content, dissolution, and moisture content of the 10 mg and 40 mg tablets did not change significantly under long-term conditions within 3 months.
Claims
1. Formula (A): 【Chemistry 1】 The compound represented by the formula (VI) is a type VI crystal, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 11.9±0.2, 20.5±0.2, 23.1±0.2, 23.9±0.2 and 24.8±0.
2.
2. The VI type crystal of the compound represented by formula (A) according to claim 1, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 9.7±0.2, 16.1±0.2, 19.3±0.2 and 21.2±0.
2.
3. The VI type crystal of the compound represented by formula (A) according to claim 2, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 1】
4. The VI type crystal of the compound represented by formula (A) according to claim 2 or 3, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 5.9±0.2, 11.0±0.2, 12.8±0.2, 14.7±0.2, 16.6±0.2, 17.8±0.2, 18.2±0.2, 18.6±0.2, 20.1±0.2, 22.0±0.2, 22.6±0.2, 26.2±0.2 and 29.0±0.
2.
5. 6. A crystalline form VI of the compound of formula (A) according to claim 1, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
6. The VI form of the compound of formula (A) according to any one of claims 1 to 5, further characterized by having a melting endothermic peak at 175±2°C in differential scanning calorimetry analysis.
7. 7. The VI form of the compound of formula (A) according to any one of claims 1 to 6, further characterized by substantially no weight loss before 200°C in thermogravimetric analysis.
8. cm in infrared absorption spectrum -1 8. A crystalline form VI of the compound of formula (A) according to any one of claims 1 to 7, further characterized by having absorption peaks at: 853±2, 1020±2, 1062±2, 1210±2, 1408±2, 1466±2, 1491±2, 1599±2, 1661±2, 3293±2.
9. 9. A crystalline form VI of the compound of formula (A) according to claim 8, further characterized in that it has an infrared absorption spectrum substantially as shown in FIG.
10. 10. The VI form of the compound of formula (A) according to any one of claims 1 to 9, further characterized by having absorption peaks in the UV spectrum at nm: 201±2, 263±2 and 306±2.
11. 11. The VI form of the compound of formula (A) according to claim 10, further characterized in that it has a UV spectrum substantially as shown in FIG.
12. A type I crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 18.3±0.2 and 24.4±0.
2.
13. The compound of formula (A) according to claim 12, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 9.6±0.2, 19.3±0.2, 21.8±0.2, 22.5±0.2 and 24.9±0.
2.
14. The I-type crystal of the compound represented by formula (A) according to claim 13, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 2】
15. The compound of formula (A) according to claim 13 or 14, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 10.7±0.2, 12.2±0.2, 16.2±0.2, 22.8±0.2, 23.4±0.2 and 27.8±0.
2.
16. 13. A crystalline form I of the compound of formula (A) according to claim 12, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
17. The crystalline form I of the compound of formula (A) according to any one of claims 12 to 16, further characterized by having a melting endothermic peak at 173±2°C in differential scanning calorimetry analysis.
18. The compound of formula (A) according to any one of claims 12 to 17, further characterized by having a weight loss of about 5.1% before 200°C in thermogravimetric analysis.
19. A type II crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 11.0±0.2, 11.6±0.2, 13.0±0.2, 17.1±0.2, 19.6±0.2, 19.8±0.2 and 22.9±0.
2.
20. The II-type crystal of the compound represented by formula (A) according to claim 19, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 3】
21. The X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 5.8±0.2, 6.4±0.2, 10.8±0.2, 14.9±0.2, 15.3±0.2, 16.4±0.2, 19.3±0.2, 20.6±0.2, 23.3±0.2, 25.1±0.2 and 26.9±0.
2. The compound of formula (A) according to claim 19 or 20, characterized in that the crystal form II is formed.
22. 20. The compound of formula (A) according to claim 19, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
4.
23. The crystalline form II of the compound of formula (A) according to any one of claims 19 to 22, further characterized by having a melting endothermic peak at 115±2°C in differential scanning calorimetry analysis.
24. The compound of formula (A) according to any one of claims 19 to 23, further characterized by having a weight loss of about 1.9% before 200°C in thermogravimetric analysis.
25. A type VII crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has characteristic peaks at least at °2θ: 11.7±0.2, 16.9±0.2, 18.3±0.2, 20.9±0.2, 21.7±0.2, 23.2±0.2, 23.8±0.2 and 27.1±0.
2.
26. The VII type crystal of the compound represented by formula (A) according to claim 25, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 13.4±0.2, 16.0±0.2, 20.7±0.2 and 22.2±0.
2.
27. A type VII crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 4】
28. The VII type crystal of the compound of formula (A) according to claim 26 or 27, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 13.2±0.2, 19.6±0.2, 21.3±0.2, 25.7±0.2 and 30.9±0.
2.
29. 26. The compound of formula (A) according to claim 25, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
24.
30. The compound of formula (A) according to any one of claims 25 to 29, further characterized by having a melting endothermic peak at 174±2°C in differential scanning calorimetry analysis.
31. The compound of formula (A) according to any one of claims 25 to 30, further characterized by having a weight loss of about 3.4% before 200°C in thermogravimetric analysis.
32. A type III crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 12.4±0.2, 14.2±0.2, 20.0±0.2 and 21.9±0.
2.
33. 33. The compound of formula (A) according to claim 32, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 7.0±0.2, 9.3±0.2, 13.9±0.2 and 24.5±0.
2.
34. The III-form crystal of the compound represented by formula (A) according to claim 33, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 5】
35. The compound of formula (A) according to claim 33 or 34, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 15.3±0.2, 20.6±0.2, 23.4±0.2, 27.5±0.2, 28.3±0.2 and 28.8±0.
2.
36. 33. A crystalline form III of the compound of formula (A) according to claim 32, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
37. The compound of formula (A) according to any one of claims 32 to 36, further characterized by having a melting endothermic peak at 173±2°C in differential scanning calorimetry analysis.
38. The compound of formula (A) according to any one of claims 32 to 37, further characterized by having a weight loss of about 3.5% before 200°C in thermogravimetric analysis.
39. A type X crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 7.0±0.2, 9.3±0.2, 12.3±0.2, 14.2±0.2, 16.3±0.2, 18.8±0.2, 19.9±0.2, 21.4±0.2 and 23.9±0.
2.
40. The X-type crystal of the compound represented by formula (A) according to claim 39, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 6】
41. The X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 15.4±0.2, 19.2±0.2, 19.5±0.2, 22.2±0.2, 23.4±0.2, 24.8±0.2, 25.8±0.2, 26.2±0.2, 26.7±0.2, 28.8±0.2 and 29.2±0.
2. The X-type crystal of the compound of formula (A) according to claim 39 or 40.
42. 40. The compound of formula (A) according to claim 39, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
27.
43. The compound of formula (A) according to any one of claims 39 to 42, further characterized by having a melting endothermic peak at 173±2°C in differential scanning calorimetry analysis.
44. The compound of formula (A) according to any one of claims 39 to 43, further characterized by having a weight loss of about 3.6% before 200°C in thermogravimetric analysis.
45. A type IV crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 9.7±0.2, 22.5±0.2, and 24.4±0.
2.
46. 46. The compound of formula (A) according to claim 45, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 6.2±0.2, 12.9±0.2, 18.4±0.2, 21.8±0.2, 23.2±0.2 and 24.8±0.
2.
47. The IV type crystal of the compound represented by formula (A) according to claim 46, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 7】
48. The IV type crystal of the compound of formula (A) according to claim 46 or 47, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 6.4±0.2, 10.8±0.2, 12.3±0.2, 16.0±0.2, 19.2±0.2, 21.1±0.2 and 27.9±0.
2.
49. 46. A crystalline form IV of the compound of formula (A) according to claim 45, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
50. 50. The compound of formula (A) according to any one of claims 45 to 49, further characterized by having endothermic peaks at 176±2°C and 251±2°C in differential scanning calorimetry analysis.
51. 51. The compound of formula (A) according to any one of claims 45 to 50, further characterized by having a weight loss of about 3.7% before 200°C in thermogravimetric analysis.
52. A type IV crystal of the compound of formula (A), characterized in that it has the following parameters: 【Table 8】
53. A type XI crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 9.7±0.2, 17.9±0.2, 19.5±0.2, 24.2±0.2 and 24.8±0.
2.
54. 54. The compound of formula (A) according to claim 53, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 7.6±0.2, 12.7±0.2, 13.2±0.2, 18.7±0.2, 18.9±0.2, 22.4±0.2 and 25.6±0.
2.
55. XI type crystal of the compound represented by formula (A) according to claim 54, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 9】
56. 56. The compound of formula (A) according to claim 54 or 55, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 14.6±0.2, 16.7±0.2, 20.2±0.2, 20.7±0.2, 21.0±0.2, 21.3±0.2, 26.0±0.2 and 29.9±0.
2.
57. 54. A crystalline form XI of the compound of formula (A) according to claim 53, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
28.
58. 58. The compound of formula (A) according to any one of claims 53 to 57, further characterized by having a melting endothermic peak at 174±2°C in differential scanning calorimetry analysis.
59. 59. The compound of formula (A) according to any one of claims 53 to 58, further characterized by having a weight loss of about 3.9% before 200°C in thermogravimetric analysis.
60. A type IX crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 9.6±0.2, 18.2±0.2, and 22.1±0.
2.
61. 61. The compound of formula (A) according to claim 60, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 6.1±0.2, 12.1±0.2, 12.4±0.2, 19.0±0.2, 19.3±0.2, 21.5±0.2, 24.4±0.2 and 24.9±0.
2.
62. The IX type crystal of the compound represented by formula (A) according to claim 61, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 10】
63. 63. The compound of formula (A) according to claim 61 or 62, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 10.5±0.2, 16.1±0.2, 20.6±0.2, 21.2±0.2, 23.6±0.2, 26.9±0.2, 27.7±0.2 and 28.4±0.
2.
64. 61. A crystalline form IX of the compound of formula (A) according to claim 60, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
26.
65. 65. The compound of formula (A) according to any one of claims 60 to 64, further characterized by having a melting endothermic peak at 174±2°C in differential scanning calorimetry analysis.
66. 66. The compound of formula (A) according to any one of claims 60 to 65, further characterized by having a weight loss of about 5.8% before 200°C in thermogravimetric analysis.
67. A V-type crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 9.4±0.2, 18.1±0.2, 18.9±0.2, 21.3±0.2 and 23.6±0.
2.
68. 68. The compound of formula (A) according to claim 67, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 24.3±0.2 and 26.8±0.
2.
69. The V-type crystal of the compound represented by formula (A) according to claim 68, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 11】
70. The V-type crystal of the compound of formula (A) according to claim 68 or 69, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 9.9±0.2, 11.8±0.2, 15.6±0.2, 15.9±0.2, 17.6±0.2, 18.4±0.2, 19.1±0.2, 19.8±0.2, 21.8±0.2 and 23.2±0.
2.
71. 68. A crystalline form V of the compound of formula (A) according to claim 67, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
72. 72. The compound of formula (A) according to any one of claims 67 to 71, further characterized by having a melting endothermic peak at 173±2°C in differential scanning calorimetry analysis.
73. 73. The compound of formula (A) according to any one of claims 67 to 72, further characterized by having a weight loss of about 6.5% before 200°C in thermogravimetric analysis.
74. A type VIII crystal of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 9.6±0.2, 12.7±0.2, 18.3±0.2, 19.1±0.2, 22.8±0.2 and 24.3±0.
2.
75. The VIII type crystal of the compound represented by formula (A) according to claim 74, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 12】
76. The X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 10.7±0.2, 12.1±0.2, 19.4±0.2, 21.8±0.2, 22.5±0.2, 24.7±0.2 and 27.6±0.
2. The compound of formula (A) according to claim 74 or 75, wherein the VIII type crystal is further characterized by the following peaks:
77. 75. A crystalline form VIII of the compound of formula (A) according to claim 74, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
25.
78. A type I crystal of the p-toluenesulfonate (1:1) salt of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 7.4±0.2, 10.2±0.2, 21.3±0.2 and 21.9±0.
2.
79. 79. The compound of formula (A) according to claim 78, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains a characteristic peak located at °2θ:27.9±0.
2. A type I crystal of the p-toluenesulfonate salt (1:1) of the compound of formula (A).
80. The I-type crystal of the p-toluenesulfonate (1:1) salt of the compound represented by formula (A) according to claim 79, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 13】
81. 81. The compound of formula (A) according to claim 79 or 80, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 14.9±0.2, 16.3±0.2, 19.2±0.2 and 23.0±0.
2. Form I crystals of the p-toluenesulfonate salt (1:1) of the compound of formula (A).
82. 79. A crystal of Form I of the p-toluenesulfonate (1:1) salt of the compound of formula (A) according to claim 78, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
37.
83. 83. A crystal of Form I of the p-toluenesulfonate (1:1) salt of the compound of formula (A) according to any one of claims 78 to 82, further characterized by having a melting endothermic peak at 236±2°C in differential scanning calorimetry analysis.
84. Form I crystals of the p-toluenesulfonate (1:1) salt of the compound of formula (A) according to any one of claims 78 to 83, further characterized by having a weight loss of about 0.1% before 200 ° C. in thermogravimetric analysis.
85. A type I crystal of the benzenesulfonate salt (1:1) of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 7.6±0.2, 10.2±0.2, and 22.8±0.
2.
86. 86. The compound of formula (A) according to claim 85, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks located at °2θ: 16.4±0.2, 19.1±0.2, 19.9±0.2, 21.3±0.2, 21.9±0.2 and 23.3±0.
2. Form I crystal of the benzenesulfonate salt (1:1) of the compound of formula (A).
87. The I-type crystal of the benzenesulfonate (1:1) of the compound represented by formula (A) according to claim 86, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 14】
88. 88. The compound of formula (A) according to claim 86 or 87, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 20.5±0.2, 21.6±0.2 and 25.0±0.
2. Form I crystal of the benzenesulfonate salt (1:1) of the compound of formula (A).
89. 86. A crystal of form I of the benzenesulfonate (1:1) salt of the compound of formula (A) according to claim 85, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
90. The benzenesulfonate (1:1) form I crystal of the compound of formula (A) according to any one of claims 85 to 89, further characterized by having a melting endothermic peak at 253±2°C in differential scanning calorimetry analysis.
91. Form I crystals of the benzenesulfonate (1:1) salt of the compound of formula (A) according to any one of claims 85 to 90, further characterized by having a weight loss of about 0.5% before 200 ° C. in thermogravimetric analysis.
92. A type I crystal of the hydrochloride salt of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 6.5±0.2, 13.8±0.2, 18.7±0.2 and 23.3±0.
2.
93. 93. The compound of formula (A) according to claim 92, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 11.3±0.2, 15.7±0.2, 16.4±0.2, 21.9±0.2, 22.7±0.2, 24.2±0.2 and 28.6±0.
2.
94. The I-type crystal of the hydrochloride salt of the compound represented by formula (A) according to claim 93, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 15】
95. 95. The compound of formula (A) according to claim 93 or 94, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 16.8±0.2, 19.7±0.2, 20.8±0.2, 21.3±0.2, 25.2±0.2 and 35.0±0.
2.
96. 93. A crystalline form I of the hydrochloride salt of the compound of formula (A) according to claim 92, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
97. The crystalline form I of the hydrochloride salt of the compound of formula (A) according to claims 92 to 96, further characterized by having a melting endothermic peak at 229±2°C in differential scanning calorimetry analysis.
98. Crystalline Form I of the hydrochloride salt of the compound of formula (A) according to any one of claims 92 to 97, further characterized by having a weight loss of about 0.7% before 175°C in thermogravimetric analysis.
99. A type I crystal of the mesylate (1:2) of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains at least characteristic peaks located at °2θ: 19.7±0.2 and 23.7±0.
2.
100. 99. The mesylate (1:2) form I crystal of the compound of formula (A) according to claim 99, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 4.7±0.2, 16.4±0.2, 18.7±0.2, 19.2±0.2, 22.3±0.2 and 22.7±0.
2.
101. The I-form crystal of the mesylate (1:2) of the compound represented by formula (A) according to claim 100, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 16】
102. 102. The compound of formula (A) mesylate (1:2) according to claim 100 or 101, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 20.1±0.2, 28.1±0.2 and 37.1±0.
2.
103. 99. A crystalline form I of the mesylate (1:2) salt of the compound of formula (A) according to claim 99, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
104. Crystalline form I of the mesylate (1:2) salt of the compound of formula (A) according to any one of claims 99 to 103, further characterized by a melting endotherm peak at 206±2°C in differential scanning calorimetry analysis.
105. Crystalline form I of the mesylate (1:2) salt of the compound of formula (A) according to any one of claims 99 to 104, further characterized by having a weight loss of about 0.7% before 200°C in thermogravimetric analysis.
106. A type I crystal of the hydrobromide salt of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 6.4±0.2, 13.5±0.2, 20.6±0.2, 21.1±0.2, 23.8±0.2, 24.0±0.2 and 26.1±0.
2.
107. The I-type crystal of the hydrobromide salt of the compound represented by formula (A) according to claim 106, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 17】
108. 108. A form I crystal of the hydrobromide salt of the compound of formula (A) according to claim 106 or 107, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation further contains characteristic peaks at °2θ: 13.0±0.2 and 28.5±0.
2.
109. 107. A crystalline form I of the hydrobromide salt of the compound of formula (A) according to claim 106, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
44.
110. 110. A crystalline form I of the hydrobromide salt of the compound of formula (A) according to any one of claims 106 to 109, further characterized by having a melting endotherm peak at 251±2°C in differential scanning calorimetry analysis.
111. 111. A crystalline form I of the hydrobromide salt of the compound of formula (A) according to any one of claims 106 to 110, further characterized by having a weight loss of about 0.6% before 200°C in thermogravimetric analysis.
112. A type II crystal of the p-toluenesulfonate (1:1) salt of the compound represented by formula (A), characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation contains characteristic peaks at least at °2θ: 6.4±0.2, 7.4±0.2, 10.2±0.2, 16.3±0.2, 21.3±0.2 and 21.8±0.
2.
113. The crystal form II of the p-toluenesulfonate (1:1) of the compound represented by formula (A) according to claim 112, characterized in that the X-ray powder diffraction pattern obtained using CuKα radiation has the following characteristic peaks: 【Table 18】
114. 113. A crystal of p-toluenesulfonate (1:1) form II of the compound of formula (A) according to claim 112, characterized in that it has an X-ray powder diffraction pattern substantially as shown in FIG.
115. 114. A crystal of Form II of the p-toluenesulfonate (1:1) salt of the compound of formula (A) according to any one of claims 112 to 113, further characterized by having a melting endothermic peak at 234±2°C in differential scanning calorimetry analysis.
116. Crystalline form II of the p-toluenesulfonate (1:1) salt of the compound of formula (A) according to any one of claims 112 to 114, further characterized by having a weight loss of about 0.2% before 200°C in thermogravimetric analysis.
117. Method for preparing a compound of formula (A): 【Chemistry 2】 And, wherein X is a halogen; preferably, I or Br; more preferably, I; A process comprising reacting a compound of formula (B), its boronic acid hydrolysis product, or a mixture of the two, with a 2-halopyrazine in the presence of a palladium catalyst and a base in DMSO or DMF.
118. 118. The method of claim 117, wherein the DMSO or DMF contains water in a volume ratio of 0.01 to 0.5:1; preferably 0.05 to 0.2:1, preferably 0.067:1, 0.1:1, or 0.2:
1.
119. 119. The method of claim 117 or 118, wherein the base is selected from sodium phosphate, potassium phosphate, sodium carbonate, potassium carbonate, cesium carbonate, a quaternary ammonium salt, NaF, KF, CsF, sodium bicarbonate, potassium bicarbonate, sodium phosphate dibasic, or potassium phosphate dibasic.
120. 120. The method of claim 119, wherein the quaternary ammonium salt is selected from organic quaternary ammonium salts including tetrabutylammonium fluoride, tetrabutylammonium bromide, tetraethylammonium fluoride, tetraethylammonium bromide, tetramethylammonium fluoride, tetramethylammonium bromide, or tetramethylammonium chloride; preferably tetrabutylammonium fluoride.
121. 118. The method of claim 117, wherein the base is selected from sodium phosphate, potassium phosphate, sodium carbonate, potassium carbonate, cesium carbonate, tetrabutylammonium fluoride, NaF, KF, or CsF.
122. 122. The process according to any one of claims 117 to 121, wherein the palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, palladium acetate, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium, palladium dichloride or bis(triphenylphosphine)palladium dichloride; preferably 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or bis(triphenylphosphine)palladium dichloride; preferably 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride.
123. 123. The method according to any one of claims 117 to 122, wherein the molar ratio of 2-halopyrazine to compound B or its boronic acid hydrolysis product or a mixture of the two is 0.8 to 1.5:1; preferably 1.2:
1.
124. 124. The method of any one of claims 117 to 123, wherein the amount of base is 1 to 3.5 times; preferably 1.2 to 2.7 times; preferably 1.2 times, 1.5 times, 1.8 times, 2.0 times, 2.1 times, 2.2 times, 2.4 times or 2.7 times the amount of compound B or its boronic acid hydrolysis product or a mixture of the two.
125. 125. The method of any one of claims 117 to 124, wherein the amount of palladium catalyst is 0.005 to 0.1 times; preferably 0.01 to 0.05 times; preferably 0.01 times, 0.02 times, 0.03 times, 0.04 times or 0.05 times the amount of compound B or its boronic acid hydrolysis product or a mixture of the two.
126. 126. The process according to any one of claims 117 to 125, wherein the reaction is carried out at a temperature between room temperature and solvent reflux, preferably at 30 to 80°C, or more preferably at 30±5°C, 50±5°C, 65±5°C or 80±5°C; preferably for a reaction time of at least 1 hour, preferably at least 3 hours.
127. Method for preparing a compound of formula (A): 【Chemistry 3】 And, wherein X is a halogen; preferably, I or Br; more preferably, I; A process comprising reacting a compound of formula (B), its boronic acid hydrolysis product, or a mixture of the two, with a 2-halopyrazine in the presence of a palladium catalyst and a quaternary ammonium salt.
128. 128. The method of claim 127, wherein the quaternary ammonium salt is selected from organic quaternary ammonium salts including tetrabutylammonium fluoride, tetrabutylammonium bromide, tetraethylammonium fluoride, tetraethylammonium bromide, tetramethylammonium fluoride, tetramethylammonium bromide, or tetramethylammonium chloride; preferably tetrabutylammonium fluoride.
129. 129. The method according to claim 127 or 128, wherein the palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, palladium acetate, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium, palladium dichloride or bis(triphenylphosphine)palladium dichloride; preferably 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride, tetrakis(triphenylphosphine)palladium, tris(dibenzylideneacetone)dipalladium or bis(triphenylphosphine)palladium dichloride; preferably 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride.
130. 130. The method according to any one of claims 127 to 129, wherein the molar ratio of 2-halopyrazine to compound B or its boronic acid hydrolysis product or a mixture of the two is 0.8 to 1.5:1; preferably 1.2:
1.
131. 131. The method of any one of claims 127 to 130, wherein the amount of base is 1 to 3.5 times; preferably 1.2 to 2.7 times; preferably 1.2 times, 1.5 times, 1.8 times, 2.0 times, 2.1 times, 2.2 times, 2.4 times or 2.7 times the amount of compound B or its boronic acid hydrolysis product or a mixture of the two.
132. 132. The method of any one of claims 127 to 131, wherein the amount of palladium catalyst is 0.005 to 0.1 times; preferably 0.01 to 0.05 times; preferably 0.01 times, 0.02 times, 0.03 times, 0.04 times or 0.05 times the amount of compound B or its boronic acid hydrolysis product or a mixture of the two.
133. 133. The process according to any one of claims 127 to 132, wherein the reaction is carried out in a solvent selected from DCM, DCE, ethyl acetate, methyl acetate, isopropyl acetate, n-hexane, n-heptane, petroleum ether, acetone, acetonitrile, toluene, methyl tert-butyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, isopropanol, water, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, DMF, DMA, DMSO, or mixtures thereof; preferably, the solvent is selected from tetrahydrofuran, 2-methyltetrahydrofuran, ethylene glycol monomethyl ether, isopropanol, water, toluene, DMF, DMSO, or mixtures thereof; preferably, the solvent is tetrahydrofuran, DMF, isopropanol, water, toluene, DMF, DMSO, or mixtures thereof.
134. 134. The process according to any one of claims 127 to 133, wherein the reaction is carried out at a temperature between room temperature and solvent reflux, preferably at 30 to 80°C, or more preferably at 30±5°C, 50±5°C, 65±5°C or 80±5°C; preferably for a reaction time of at least 1 hour, preferably at least 3 hours.
135. Methods for preparing compound B or its boronic acid hydrolysis product or a mixture of the two: 【Chemistry 4】 And, Palladium catalyst Pd(dppf)Cl 2 and reacting a compound of formula (C) with bis(pinacolato)diboron in the presence of acetate in a solvent, wherein the solvent is selected from DMSO, DCM, DCE, ethyl acetate, methyl acetate, isopropyl acetate, acetone, acetonitrile, methyl tert-butyl ether, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, DMF or DMA; preferably DMSO, ethylene glycol monomethyl ether or DMF; preferably DMSO.
136. 136. The method of claim 135, wherein the acetate is selected from potassium acetate, sodium acetate or cesium acetate; preferably potassium acetate.
137. The method of claim 135 or 136, wherein the amount of acetate is 2 to 5 times that of compound C; preferably 2.5 times.
138. 138. The method according to any one of claims 135 to 137, wherein the amount of bis(pinacolato)diboron is 3 to 6 times that of compound C; preferably 3 times.
139. The method according to any one of claims 135 to 138, wherein the amount of the catalyst is 0.01 to 0.1 times, preferably 0.05 times, that of compound C.
140. The reaction is carried out at a temperature of from 60° C. to the solvent reflux temperature, preferably from 60 to 100 o C, or more preferably at 80±10° C; preferably for a reaction time of at least 1 hour, preferably for at least 2 hours.
141. Ingredients include: (i) a crystal according to any one of claims 1 to 16, (ii) a diluent, (iii) a disintegrant, (iv) a glidant, and (v) lubricants, 23. A pharmaceutical composition comprising:
142. The pharmaceutical composition of claim 141, wherein the crystalline form is 1% to 30% by weight, preferably 5% to 20% by weight, preferably 8% to 15% by weight, or more preferably about 10% by weight of the total weight of the pharmaceutical composition based on the weight of the free base of the compound; preferably, wherein the amount of crystalline form in a unit dose is 1 to 100 mg, preferably 5 to 50 mg, preferably 8 to 40 mg, preferably about 10 mg, 20 mg, 30 mg or 40 mg.
143. 143. The pharmaceutical composition according to any one of claims 141 to 142, wherein the diluent represents 65% to 95% by weight, preferably 70% to 90% by weight, preferably about 80%, 81%, 82%, 83%, 84% or 85% by weight of the total weight of the pharmaceutical composition; preferably wherein the amount of diluent in a unit dose is 65 to 380 mg, preferably 70 to 360 mg, preferably 80 to 350 mg, for example about 83 mg or 332 mg.
144. 144. A pharmaceutical composition according to any one of claims 141 to 143, wherein the diluent is selected from lactose monohydrate, microcrystalline cellulose, anhydrous calcium hydrogen phosphate, mannitol and pregelatinised starch, and mixtures thereof; preferably, when both lactose monohydrate and microcrystalline cellulose are present, the weight ratio of lactose monohydrate to microcrystalline cellulose is from 5:1 to 1:5, preferably from 2:1 to 1:3, preferably about 1:2, for example 1:1.
96.
145. 145. The pharmaceutical composition according to any one of claims 141 to 144, wherein the disintegrant is present in an amount of 1% to 5% by weight, preferably 2% to 4% by weight, preferably about 3% by weight, of the total weight of the pharmaceutical composition; preferably wherein the amount of disintegrant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
146. 146. The pharmaceutical composition of any one of claims 141 to 145, wherein the disintegrant is croscarmellose sodium.
147. 147. The pharmaceutical composition according to any one of claims 141 to 146, wherein the glidant is present in an amount of 1% to 5% by weight, preferably 2% to 4% by weight, preferably about 3% by weight, of the total weight of the pharmaceutical composition; preferably wherein the amount of (iv) glidant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
148. 148. The pharmaceutical composition of any one of claims 141 to 147, wherein the glidant is colloidal silica.
149. 149. The pharmaceutical composition according to any one of claims 141 to 148, wherein the lubricant is present in an amount of 0.1% to 5% by weight, preferably 0.5% to 2% by weight, preferably about 1% by weight, of the total weight of the pharmaceutical composition; and preferably wherein the amount of (v) lubricant in a unit dose is 0.1 to 20 mg, preferably 0.5 to 8 mg, preferably about 1 mg, 2 mg, 3 mg or 4 mg.
150. The pharmaceutical composition according to any one of claims 141 to 149, wherein the lubricant is magnesium stearate or sodium stearyl fumarate.
151. Ingredients include: (i) 1% by weight to 30% by weight of a VI type crystal of Compound A; (ii) 70% to 90% by weight of lactose monohydrate and microcrystalline cellulose (weight ratio 1:2); (iii) 2% to 4% by weight of croscarmellose sodium; (iv) 2% to 4% by weight of colloidal silica, and (v) 0.1% to 5% by weight of magnesium stearate; 151. The pharmaceutical composition according to any one of claims 141 to 150, comprising:
152. A unit dose of the following ingredients: (i) about 10 mg of type VI crystal of Compound A; (ii) about 28 mg lactose monohydrate and about 55 mg microcrystalline cellulose; (iii) about 3 mg of croscarmellose sodium; (iv) about 3 mg of colloidal silica, and (v) about 1 mg of magnesium stearate; 152. The pharmaceutical composition of claim 151, comprising:
153. A unit dose of the following ingredients: (i) about 40 mg of type VI crystal of Compound A; (ii) about 112 mg lactose monohydrate and about 220 mg microcrystalline cellulose; (iii) about 12 mg of croscarmellose sodium; (iv) about 12 mg of colloidal silica, and (v) about 4 mg magnesium stearate; 152. The pharmaceutical composition of claim 151, comprising:
154. The pharmaceutical composition according to any one of claims 141 to 153, which is a tablet, preferably a coated tablet.
155. (i) a compound represented by formula (A), (ii) a diluent, (iii) a disintegrant, (iv) a glidant, and (v) lubricants, A pharmaceutical composition comprising: The pharmaceutical composition, wherein the diluent is present in an amount of from 1% to 5% by weight, preferably from 2% to 4% by weight, preferably about 3% by weight, of the total weight of the pharmaceutical composition.
156. 156. The pharmaceutical composition of claim 155, wherein the glidant is colloidal silica.
157. 157. The pharmaceutical composition according to claim 155 or 156, wherein the amount of the glidant in a unit dose is between 1 and 20 mg, preferably between 2 and 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
158. 158. The pharmaceutical composition according to any one of claims 155 to 157, wherein the diluent is 65% to 95% by weight, preferably 70% to 90% by weight, preferably about 80%, 81%, 82%, 83%, 84% or 85% by weight of the total weight of the pharmaceutical composition; preferably wherein the amount of diluent in a unit dose is 65 to 380 mg, preferably 70 to 360 mg, preferably 80 to 350 mg, for example about 83 mg or 332 mg.
159. 159. A pharmaceutical composition according to any one of claims 155 to 158, wherein the diluent is selected from lactose monohydrate, microcrystalline cellulose, anhydrous calcium hydrogen phosphate, mannitol and pregelatinised starch, and mixtures thereof; preferably, wherein, if both lactose monohydrate and microcrystalline cellulose are present, the weight ratio of lactose monohydrate to microcrystalline cellulose is from 5:1 to 1:5, preferably from 2:1 to 1:3, preferably about 1:2, for example 1:1.
96.
160. 160. The pharmaceutical composition according to any one of claims 155 to 159, wherein the disintegrant is present in an amount of 1% to 5% by weight, preferably 2% to 4% by weight, preferably about 3% by weight, of the total weight of the pharmaceutical composition; preferably wherein the amount of disintegrant in a unit dose is 1 to 20 mg, preferably 2 to 16 mg, preferably about 3 mg, 6 mg, 9 mg or 12 mg.
161. 161. The pharmaceutical composition of any one of claims 155 to 160, wherein the disintegrant is croscarmellose sodium.
162. 162. The pharmaceutical composition according to any one of claims 155 to 161, wherein the lubricant is present in an amount of 0.1% to 5% by weight, preferably 0.5% to 2% by weight, preferably about 1% by weight, of the total weight of the pharmaceutical composition; preferably wherein the amount of lubricant in a unit dose is 0.1 to 20 mg, preferably 0.5 to 8 mg, preferably about 1 mg, 2 mg, 3 mg or 4 mg.
163. 163. The pharmaceutical composition of any one of claims 155-162, wherein the lubricant is magnesium stearate or sodium stearyl fumarate.
164. Use of a crystalline form of the compound of formula (A) according to any one of claims 1 to 116 in the manufacture of a medicament for treating and / or preventing a disease caused by Bcr-Abl.
165. Use of the crystalline form of the compound of formula (A) according to any one of claims 1 to 116 in the manufacture of a medicament for treating and / or preventing the following diseases: solid tumors, sarcomas, acute lymphocytic leukemia, acute myeloid leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, gastrointestinal stromal tumors, thyroid cancer, gastric cancer, rectal cancer, multiple myeloma, oncoses and other proliferative diseases; or the Bcr-Abl1 mediated disease is metastatic invasive cancer, viral infection or CNS disorder.
166. A crystalline form of the compound of formula (A) according to any one of claims 1 to 116 for use in the treatment and / or prevention of diseases caused by Bcr-Abl.
167. A crystalline form of the compound of formula (A) according to any one of claims 1 to 116 for use in the treatment and / or prophylaxis of solid tumors, sarcomas, acute lymphocytic leukemia, acute myeloid leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, gastrointestinal stromal tumors, thyroid cancer, gastric cancer, rectal cancer, multiple myeloma, oncoses, and other proliferative diseases; or the Bcr-Abl1 mediated disease is metastatic invasive cancer, viral infection, or CNS disorder.
168. A method for treating and / or preventing a Bcr-Abl mediated disease in a subject, comprising administering to said subject a crystalline form of a compound according to any one of claims 1 to 116.
169. A method for treating and / or preventing the following diseases in a subject, comprising administering to a subject a crystalline form of a compound of formula (A) according to any one of claims 1 to 116: solid tumors, sarcomas, acute lymphocytic leukemia, acute myeloid leukemia, chronic lymphocytic leukemia, chronic myeloid leukemia, gastrointestinal stromal tumors, thyroid cancer, gastric cancer, rectal cancer, multiple myeloma, oncoses, and other proliferative diseases; or the Bcr-Abl1 mediated disease is metastatic invasive cancer, viral infection, or CNS disorder.
Citation Information
Patent Citations
Substitutive nicotinamide compound, medicine composition and application of composition
CN109651359A
Fused bicyclic heteroaryl derivatives as phd inhibitors
JP2018512408A
(Hetero)arylamide-based compounds for inhibiting protein kinase activity
JP2020506965A
Solid forms of pyrazine-substituted nicotinamides and their preparation and use
JP7612229B2
Compounds and methods of use
WO2010080478A1